Data from: Adaptation to parasites and costs of parasite resistance in mutator and non-mutator bacteria - Wielgoss, Sébastien; Bergmiller, Tobias; Bischofberger, Anna M.; Hall, Alex R.
Parasitism creates selection for resistance mechanisms in host populations and is hypothesized to promote increased host evolvability. However, the influence of these traits on host evolution when parasites are no longer present is unclear. We used experimental evolution and whole-genome sequencing of Escherichia coli to determine the effects of past and present exposure to parasitic viruses (phages) on the spread of mutator alleles, resistance, and bacterial competitive fitness. We found that mutator alleles spread rapidly during adaptation to any of four different phage species, and this pattern was even more pronounced with multiple phages present simultaneously. However, hypermutability did not detectably accelerate adaptation in the absence of phages and recovery of fitness costs associated with resistance. Several lineages evolved phage resistance through elevated mucoidy, and during subsequent evolution in phage-free conditions they rapidly reverted to nonmucoid, phage-susceptible phenotypes. Genome sequencing revealed that this phenotypic reversion was achieved by additional genetic changes rather than by genotypic reversion of the initial resistance mutations. Insertion sequence (IS) elements played a key role in both the acquisition of resistance and adaptation in the absence of parasites; unlike single nucleotide polymorphisms, IS insertions were not more frequent in mutator lineages. Our results provide a genetic explanation for rapid reversion of mucoidy, a phenotype observed in other bacterial species including human pathogens. Moreover, this demonstrates that the types of genetic change underlying adaptation to fitness costs, and consequently the impact of evolvability mechanisms such as increased point-mutation rates, depend critically on the mechanism of resistance.

Learning with attributes for object recognition: Parametric and non-parametrics views - Sharmanska, Viktoriia
The human ability to recognize objects in complex scenes has driven research in the computer vision field over couple of decades. This thesis focuses on the object recognition task in images. That is, given the image, we want the computer system to be able to predict the class of the object that appears in the image. A recent successful attempt to bridge semantic understanding of the image perceived by humans and by computers uses attribute-based models. Attributes are semantic properties of the objects shared across different categories, which humans and computers can decide on. To explore the attribute-based models we take a statistical machine learning approach, and address two key learning challenges in view of object recognition task: learning augmented attributes as mid-level discriminative feature representation, and learning with attributes as privileged information. Our main contributions are parametric and non-parametric models and algorithms to solve these frameworks. In the parametric approach, we explore an autoencoder model combined with the large margin nearest neighbor principle for mid-level feature learning, and linear support vector machines for learning with privileged information. In the non-parametric approach, we propose a supervised Indian Buffet Process for automatic augmentation of semantic attributes, and explore the Gaussian Processes classification framework for learning with privileged information. A thorough experimental analysis shows the effectiveness of the proposed models in both parametric and non-parametric views.

Biological auctions with multiple rewards - Reiter, Johannes; Kanodia, Ayush; Gupta, Raghav; Nowak, Martin; Chatterjee, Krishnendu (Proceedings of the Royal Society of London Series B Biological Sciences)
The competition for resources among cells, individuals or species is a fundamental characteristic of evolution. Biological all-pay auctions have been used to model situations where multiple individuals compete for a single resource. However, in many situations multiple resources with various values exist and single reward auctions are not applicable. We generalize the model to multiple rewards and study the evolution of strategies. In biological all-pay auctions the bid of an individual corresponds to its strategy and is equivalent to its payment in the auction. The decreasingly ordered rewards are distributed according to the decreasingly ordered bids of the participating individuals. The reproductive success of an individual is proportional to its fitness given by the sum of the rewards won minus its payments. Hence, successful bidding strategies spread in the population. We find that the results for the multiple reward case are very different from the single reward case. While the mixed strategy equilibrium in the single reward case with more than two players consists of mostly low-bidding individuals, we show that the equilibrium can convert to many high-bidding individuals and a few low-bidding individuals in the multiple reward case. Some reward values lead to a specialization among the individuals where one subpopulation competes for the rewards and the other subpopulation largely avoids costly competitions. Whether the mixed strategy equilibrium is an evolutionarily stable strategy (ESS) depends on the specific values of the rewards.

The subclonal evolution of cancer - Reiter, Johannes
Cancer results from an uncontrolled growth of abnormal cells. Sequentially accumulated genetic and epigenetic alterations decrease cell death and increase cell replication. We used mathematical models to quantify the effect of driver gene mutations. The recently developed targeted therapies can lead to dramatic regressions. However, in solid cancers, clinical responses are often short-lived because resistant cancer cells evolve. We estimated that approximately 50 different mutations can confer resistance to a typical targeted therapeutic agent. We find that resistant cells are likely to be present in expanded subclones before the start of the treatment. The dominant strategy to prevent the evolution of resistance is combination therapy. Our analytical results suggest that in most patients, dual therapy, but not monotherapy, can result in long-term disease control. However, long-term control can only occur if there are no possible mutations in the genome that can cause cross-resistance to both drugs. Furthermore, we showed that simultaneous therapy with two drugs is much more likely to result in long-term disease control than sequential therapy with the same drugs. To improve our understanding of the underlying subclonal evolution we reconstruct the evolutionary history of a patient's cancer from next-generation sequencing data of spatially-distinct DNA samples. Using a quantitative measure of genetic relatedness, we found that pancreatic cancers and their metastases demonstrated a higher level of relatedness than that expected for any two cells randomly taken from a normal tissue. This minimal amount of genetic divergence among advanced lesions indicates that genetic heterogeneity, when quantitatively defined, is not a fundamental feature of the natural history of untreated pancreatic cancers. Our newly developed, phylogenomic tool Treeomics finds evidence for seeding patterns of metastases and can directly be used to discover rules governing the evolution of solid malignancies to transform cancer into a more predictable disease.

A Koksma-Hlawka inequality for general discrepancy systems - Pausinger, Florian; Svane, Anne (Journal of Complexity)
Motivated by recent ideas of Harman (Unif. Distrib. Theory, 2010) we develop a new concept of variation of multivariate functions on a compact Hausdorff space with respect to a collection D of subsets. We prove a general version of the Koksma-Hlawka theorem that holds for this notion of variation and discrepancy with respect to D. As special cases, we obtain Koksma-Hlawka inequalities for classical notions, such as extreme or isotropic discrepancy. For extreme discrepancy, our result coincides with the usual Koksma-Hlawka theorem. We show that the space of functions of bounded D-variation contains important discontinuous functions and is closed under natural algebraic operations. Finally, we illustrate the results on concrete integration problems from integral geometry and stereology.

On the approximation of intrinsic volumes - Pausinger, Florian
This thesis is concerned with the computation and approximation of intrinsic volumes. Given a smooth body M and a certain digital approximation of it, we develop algorithms to approximate various intrinsic volumes of M using only measurements taken from its digital approximations. The crucial idea behind our novel algorithms is to link the recent theory of persistent homology to the theory of intrinsic volumes via the Crofton formula from integral geometry and, in particular, via Euler characteristic computations. Our main contributions are a multigrid convergent digital algorithm to compute the first intrinsic volume of a solid body in R^n as well as an appropriate integration pipeline to approximate integral-geometric integrals defined over the Grassmannian manifold.

Dynamics of transcription factor binding site evolution - Tugrul, Murat; Paixao, Tiago; Barton, Nicholas H; Tkacik, Gasper (PLoS Genetics)
Evolution of gene regulation is crucial for our understanding of the phenotypic differences between species, populations and individuals. Sequence-specific binding of transcription factors to the regulatory regions on the DNA is a key regulatory mechanism that determines gene expression and hence heritable phenotypic variation. We use a biophysical model for directional selection on gene expression to estimate the rates of gain and loss of transcription factor binding sites (TFBS) in finite populations under both point and insertion/deletion mutations. Our results show that these rates are typically slow for a single TFBS in an isolated DNA region, unless the selection is extremely strong. These rates decrease drastically with increasing TFBS length or increasingly specific protein-DNA interactions, making the evolution of sites longer than ∼ 10 bp unlikely on typical eukaryotic speciation timescales. Similarly, evolution converges to the stationary distribution of binding sequences very slowly, making the equilibrium assumption questionable. The availability of longer regulatory sequences in which multiple binding sites can evolve simultaneously, the presence of “pre-sites” or partially decayed old sites in the initial sequence, and biophysical cooperativity between transcription factors, can all facilitate gain of TFBS and reconcile theoretical calculations with timescales inferred from comparative genomics.

Complete composition operators for IOCO-testing theory - Beneš, Nikola; Daca, Przemyslaw; Henzinger, Thomas A; Kretinsky, Jan; Nickovic, Dejan
We extend the theory of input-output conformance with operators for merge and quotient. The former is useful when testing against multiple requirements or views. The latter can be used to generate tests for patches of an already tested system. Both operators can combine systems with different action alphabets, which is usually the case when constructing complex systems and specifications from parts, for instance different views as well as newly defined functionality of a~previous version of the system.

CEGAR for compositional analysis of qualitative properties in Markov decision processes - Chatterjee, Krishnendu; Chmelik, Martin; Daca, Przemyslaw (Formal Methods in System Design)
We consider Markov decision processes (MDPs) which are a standard model for probabilistic systems. We focus on qualitative properties for MDPs that can express that desired behaviors of the system arise almost-surely (with probability 1) or with positive probability. We introduce a new simulation relation to capture the refinement relation of MDPs with respect to qualitative properties, and present discrete graph algorithms with quadratic complexity to compute the simulation relation. We present an automated technique for assume-guarantee style reasoning for compositional analysis of two-player games by giving a counterexample guided abstraction-refinement approach to compute our new simulation relation. We show a tight link between two-player games and MDPs, and as a consequence the results for games are lifted to MDPs with qualitative properties. We have implemented our algorithms and show that the compositional analysis leads to significant improvements.

Faster algorithms for algebraic path properties in recursive state machines with constant treewidth - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Pavlogiannis, Andreas; Goyal, Prateesh (ACM SIGPLAN Notices)
Interprocedural analysis is at the heart of numerous applications in programming languages, such as alias analysis, constant propagation, etc. Recursive state machines (RSMs) are standard models for interprocedural analysis. We consider a general framework with RSMs where the transitions are labeled from a semiring, and path properties are algebraic with semiring operations. RSMs with algebraic path properties can model interprocedural dataflow analysis problems, the shortest path problem, the most probable path problem, etc. The traditional algorithms for interprocedural analysis focus on path properties where the starting point is fixed as the entry point of a specific method. In this work, we consider possible multiple queries as required in many applications such as in alias analysis. The study of multiple queries allows us to bring in a very important algorithmic distinction between the resource usage of the one-time preprocessing vs for each individual query. The second aspect that we consider is that the control flow graphs for most programs have constant treewidth. Our main contributions are simple and implementable algorithms that supportmultiple queries for algebraic path properties for RSMs that have constant treewidth. Our theoretical results show that our algorithms have small additional one-time preprocessing, but can answer subsequent queries significantly faster as compared to the current best-known solutions for several important problems, such as interprocedural reachability and shortest path. We provide a prototype implementation for interprocedural reachability and intraprocedural shortest path that gives a significant speed-up on several benchmarks.

Quantitative interprocedural analysis - Chatterjee, Krishnendu; Pavlogiannis, Andreas; Velner, Yaron (Proceedings of the 42nd Annual ACM SIGPLAN-SIGACT)
We consider the quantitative analysis problem for interprocedural control-flow graphs (ICFGs). The input consists of an ICFG, a positive weight function that assigns every transition a positive integer-valued number, and a labelling of the transitions (events) as good, bad, and neutral events. The weight function assigns to each transition a numerical value that represents ameasure of how good or bad an event is. The quantitative analysis problem asks whether there is a run of the ICFG where the ratio of the sum of the numerical weights of good events versus the sum of weights of bad events in the long-run is at least a given threshold (or equivalently, to compute the maximal ratio among all valid paths in the ICFG). The quantitative analysis problem for ICFGs can be solved in polynomial time, and we present an efficient and practical algorithm for the problem. We show that several problems relevant for static program analysis, such as estimating the worst-case execution time of a program or the average energy consumption of a mobile application, can be modeled in our framework. We have implemented our algorithm as a tool in the Java Soot framework. We demonstrate the effectiveness of our approach with two case studies. First, we show that our framework provides a sound approach (no false positives) for the analysis of inefficiently-used containers. Second, we show that our approach can also be used for static profiling of programs which reasons about methods that are frequently invoked. Our experimental results show that our tool scales to relatively large benchmarks, and discovers relevant and useful information that can be used to optimize performance of the programs.

Faster algorithms for quantitative verification in constant treewidth graphs - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Pavlogiannis, Andreas
We consider the core algorithmic problems related to verification of systems with respect to three classical quantitative properties, namely, the mean-payoff property, the ratio property, and the minimum initial credit for energy property. The algorithmic problem given a graph and a quantitative property asks to compute the optimal value (the infimum value over all traces) from every node of the graph. We consider graphs with constant treewidth, and it is well-known that the control-flow graphs of most programs have constant treewidth. Let n denote the number of nodes of a graph, m the number of edges (for constant treewidth graphs m=O(n)) and W the largest absolute value of the weights. Our main theoretical results are as follows. First, for constant treewidth graphs we present an algorithm that approximates the mean-payoff value within a multiplicative factor of ϵ in time O(n⋅log(n/ϵ)) and linear space, as compared to the classical algorithms that require quadratic time. Second, for the ratio property we present an algorithm that for constant treewidth graphs works in time O(n⋅log(|a⋅b|))=O(n⋅log(n⋅W)), when the output is ab, as compared to the previously best known algorithm with running time O(n2⋅log(n⋅W)). Third, for the minimum initial credit problem we show that (i) for general graphs the problem can be solved in O(n2⋅m) time and the associated decision problem can be solved in O(n⋅m) time, improving the previous known O(n3⋅m⋅log(n⋅W)) and O(n2⋅m) bounds, respectively; and (ii) for constant treewidth graphs we present an algorithm that requires O(n⋅logn) time, improving the previous known O(n4⋅log(n⋅W)) bound. We have implemented some of our algorithms and show that they present a significant speedup on standard benchmarks.

A framework for automated competitive analysis of on-line scheduling of firm-deadline tasks - Chatterjee, Krishnendu; Pavlogiannis, Andreas; Kößler, Alexander; Schmid, Ulrich (Real-Time Systems Symposium)
We present a flexible framework for the automated competitive analysis of on-line scheduling algorithms for firm-deadline real-time tasks based on multi-objective graphs: Given a task set and an on-line scheduling algorithm specified as a labeled transition system, along with some optional safety, liveness, and/or limit-average constraints for the adversary, we automatically compute the competitive ratio of the algorithm w.r.t. A clairvoyant scheduler. We demonstrate the flexibility and power of our approach by comparing the competitive ratio of several on-line algorithms, including Dover, that have been proposed in the past, for various task sets. Our experimental results reveal that none of these algorithms is universally optimal, in the sense that there are task sets where other schedulers provide better performance. Our framework is hence a very useful design tool for selecting optimal algorithms for a given application.

High-resolution brittle fracture simulation with boundary elements - Hahn, David; Wojtan, Christopher J
We present a method for simulating brittle fracture under the assumptions of quasi-static linear elastic fracture mechanics (LEFM). Using the boundary element method (BEM) and Lagrangian crack-fronts, we produce highly detailed fracture surfaces. The computational cost of the BEM is alleviated by using a low-resolution mesh and interpolating the resulting stress intensity factors when propagating the high-resolution crack-front. Our system produces physics-based fracture surfaces with high spatial and temporal resolution, taking spatial variation of material toughness and/or strength into account. It also allows for crack initiation to be handled separately from crack propagation, which is not only more reasonable from a physics perspective, but can also be used to control the simulation. Separating the resolution of the crack-front from the resolution of the computational mesh increases the efficiency and therefore the amount of visual detail on the resulting fracture surfaces. The BEM also allows us to re-use previously computed blocks of the system matrix.

Cortical contractility triggers a stochastic switch to fast amoeboid cell motility - Ruprecht, Verena; Wieser, Stefan; Callan Jones, Andrew; Smutny, Michael; Morita, Hitoshi; Sako, Keisuke; Barone, Vanessa; Ritsch Marte, Monika; Sixt, Michael K; Voituriez, Raphaël; Heisenberg, Carl-Philipp J (Cell)
3D amoeboid cell migration is central to many developmental and disease-related processes such as cancer metastasis. Here, we identify a unique prototypic amoeboid cell migration mode in early zebrafish embryos, termed stable-bleb migration. Stable-bleb cells display an invariant polarized balloon-like shape with exceptional migration speed and persistence. Progenitor cells can be reversibly transformed into stable-bleb cells irrespective of their primary fate and motile characteristics by increasing myosin II activity through biochemical or mechanical stimuli. Using a combination of theory and experiments, we show that, in stable-bleb cells, cortical contractility fluctuations trigger a stochastic switch into amoeboid motility, and a positive feedback between cortical flows and gradients in contractility maintains stable-bleb cell polarization. We further show that rearward cortical flows drive stable-bleb cell migration in various adhesive and non-adhesive environments, unraveling a highly versatile amoeboid migration phenotype.

PIN-dependent auxin transport: Action, regulation, and evolution - Adamowski, Maciek; Friml, Jirí (Plant Cell)
Auxin participates in a multitude of developmental processes, as well as responses to environmental cues. Compared with other plant hormones, auxin exhibits a unique property, as it undergoes directional, cell-to-cell transport facilitated by plasma membrane-localized transport proteins. Among them, a prominent role has been ascribed to the PIN family of auxin efflux facilitators. PIN proteins direct polar auxin transport on account of their asymmetric subcellular localizations. In this review, we provide an overview of the multiple developmental roles of PIN proteins, including the atypical endoplasmic reticulum-localized members of the family, and look at the family from an evolutionary perspective. Next, we cover the cell biological and molecular aspects of PIN function, in particular the establishment of their polar subcellular localization. Hormonal and environmental inputs into the regulation of PIN action are summarized as well.

The local semicircle law for random matrices with a fourfold symmetry - Alt, Johannes (Journal of Mathematical Physics)
We consider real symmetric and complex Hermitian random matrices with the additional symmetry hxy = hN-y,N-x. The matrix elements are independent (up to the fourfold symmetry) and not necessarily identically distributed. This ensemble naturally arises as the Fourier transform of a Gaussian orthogonal ensemble. Italso occurs as the flip matrix model - an approximation of the two-dimensional Anderson model at small disorder. We show that the density of states converges to the Wigner semicircle law despite the new symmetry type. We also prove the local version of the semicircle law on the optimal scale.

Light-assisted small-molecule screening against protein kinases - Inglés Prieto, Álvaro; Gschaider-Reichhart, Eva; Muellner, Markus; Nowak, Matthias; Nijman, Sebastian; Grusch, Michael; Janovjak, Harald L (Nature Chemical Biology)
High-throughput live-cell screens are intricate elements of systems biology studies and drug discovery pipelines. Here, we demonstrate an optogenetics-assisted method that avoids the need for chemical activators and reporters, reduces the number of operational steps and increases information content in a cell-based small-molecule screen against human protein kinases, including an orphan receptor tyrosine kinase. This blueprint for all-optical screening can be adapted to many drug targets and cellular processes.

Stochastic proofreading mechanism alleviates crosstalk in transcriptional regulation - Cepeda Humerez, Sarah A; Rieckh, Georg; Tkacik, Gasper (Physical Review Letters)
Gene expression is controlled primarily by interactions between transcription factor proteins (TFs) and the regulatory DNA sequence, a process that can be captured well by thermodynamic models of regulation. These models, however, neglect regulatory crosstalk: the possibility that noncognate TFs could initiate transcription, with potentially disastrous effects for the cell. Here, we estimate the importance of crosstalk, suggest that its avoidance strongly constrains equilibrium models of TF binding, and propose an alternative nonequilibrium scheme that implements kinetic proofreading to suppress erroneous initiation. This proposal is consistent with the observed covalent modifications of the transcriptional apparatus and predicts increased noise in gene expression as a trade-off for improved specificity. Using information theory, we quantify this trade-off to find when optimal proofreading architectures are favored over their equilibrium counterparts. Such architectures exhibit significant super-Poisson noise at low expression in steady state.

Eliminating higher-multiplicity intersections, III. Codimension 2 - Avvakumov, Sergey; Mabillard, Isaac; Skopenkov, A.; Wagner, Uli (arXiv)
We study conditions under which a finite simplicial complex $K$ can be mapped to $\mathbb R^d$ without higher-multiplicity intersections. An almost $r$-embedding is a map $f: K→ \mathbb R^d$ such that the images of any $r$ pairwise disjoint simplices of $K$ do not have a common point. We show that if $r$ is not a prime power and $d≥ 2r+1$, then there is a counterexample to the topological Tverberg conjecture, i.e., there is an almost $r$-embedding of the $(d+1)(r-1)$-simplex in $\mathbb R^d$. This improves on previous constructions of counterexamples (for $d≥ 3r$) based on a series of papers by M. \"Ozaydin, M. Gromov, P. Blagojevi\'c, F. Frick, G. Ziegler, and the second and fourth present authors. The counterexamples are obtained by proving the following algebraic criterion in codimension 2: If $r\ge3$ and if $K$ is a finite $2(r-1)$-complex then there exists an almost $r$-embedding $K→ \mathbb R^{2r}$ if and only if there exists a general position PL map $f:K→ \mathbb R^{2r}$ such that the algebraic intersection number of the $f$-images of any $r$ pairwise disjoint simplices of $K$ is zero. This result can be restated in terms of cohomological obstructions or equivariant maps, and extends an analogous codimension 3 criterion by the second and fourth authors. As another application we classify ornaments $f:S^3 \sqcup S^3\sqcup S^3→ \mathbb R^5$ up to ornament concordance. It follows from work of M. Freedman, V. Krushkal and P. Teichner that the analogous criterion for $r=2$ is false. We prove a lemma on singular higher-dimensional Borromean rings, yielding an elementary proof of the counterexample.

Algorithms for algebraic path properties in concurrent systems of constant treewidth components - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Goharshady, Amir; Pavlogiannis, Andreas
We study algorithmic questions for concurrent systems where the transitions are labeled from a complete, closed semiring, and path properties are algebraic with semiring operations. The algebraic path properties can model dataflow analysis problems, the shortest path problem, and many other natural problems that arise in program analysis. We consider that each component of the concurrent system is a graph with constant treewidth, a property satisfied by the controlflow graphs of most programs. We allow for multiple possible queries, which arise naturally in demand driven dataflow analysis. The study of multiple queries allows us to consider the tradeoff between the resource usage of the one-time preprocessing and for each individual query. The traditional approach constructs the product graph of all components and applies the best-known graph algorithm on the product. In this approach, even the answer to a single query requires the transitive closure (i.e., the results of all possible queries), which provides no room for tradeoff between preprocessing and query time. Our main contributions are algorithms that significantly improve the worst-case running time of the traditional approach, and provide various tradeoffs depending on the number of queries. For example, in a concurrent system of two components, the traditional approach requires hexic time in the worst case for answering one query as well as computing the transitive closure, whereas we show that with one-time preprocessing in almost cubic time, each subsequent query can be answered in at most linear time, and even the transitive closure can be computed in almost quartic time. Furthermore, we establish conditional optimality results showing that the worst-case running time of our algorithms cannot be improved without achieving major breakthroughs in graph algorithms (i.e., improving the worst-case bound for the shortest path problem in general graphs). Preliminary experimental results show that our algorithms perform favorably on several benchmarks.

Algorithms for algebraic path properties in concurrent systems of constant treewidth components - Anonymous, 1; Anonymous, 2; Anonymous, 3; Anonymous, 4
We study algorithmic questions for concurrent systems where the transitions are labeled from a complete, closed semiring, and path properties are algebraic with semiring operations. The algebraic path properties can model dataflow analysis problems, the shortest path problem, and many other natural properties that arise in program analysis. We consider that each component of the concurrent system is a graph with constant treewidth, and it is known that the controlflow graphs of most programs have constant treewidth. We allow for multiple possible queries, which arise naturally in demand driven dataflow analysis problems (e.g., alias analysis). The study of multiple queries allows us to consider the tradeoff between the resource usage of the one-time preprocessing and for each individual query. The traditional approaches construct the product graph of all components and apply the best-known graph algorithm on the product. In the traditional approach, even the answer to a single query requires the transitive closure computation (i.e., the results of all possible queries), which provides no room for tradeoff between preprocessing and query time. Our main contributions are algorithms that significantly improve the worst-case running time of the traditional approach, and provide various tradeoffs depending on the number of queries. For example, in a concurrent system of two components, the traditional approach requires hexic time in the worst case for answering one query as well as computing the transitive closure, whereas we show that with one-time preprocessing in almost cubic time, each subsequent query can be answered in at most linear time, and even the transitive closure can be computed in almost quartic time. Furthermore, we establish conditional optimality results that show that the worst-case running times of our algorithms cannot be improved without achieving major breakthroughs in graph algorithms (such as improving the worst-case bounds for the shortest path problem in general graphs whose current best-known bound has not been improved in five decades). Finally, we provide a prototype implementation of our algorithms which significantly outperforms the existing algorithmic methods on several benchmarks.

Temporal logic control for stochastic linear systems using abstraction refinement of probabilistic games - Svoreňová, Mária; Kretinsky, Jan; Chmelik, Martin; Chatterjee, Krishnendu; Cěrná, Ivana; Belta, Cǎlin (Proceedings of the 18th International Conference on Hybrid Systems: Computation and Control)
We consider the problem of computing the set of initial states of a dynamical system such that there exists a control strategy to ensure that the trajectories satisfy a temporal logic specification with probability 1 (almost-surely). We focus on discrete-time, stochastic linear dynamics and specifications given as formulas of the Generalized Reactivity(1) fragment of Linear Temporal Logic over linear predicates in the states of the system. We propose a solution based on iterative abstraction-refinement, and turn-based 2-player probabilistic games. While the theoretical guarantee of our algorithm after any finite number of iterations is only a partial solution, we show that if our algorithm terminates, then the result is the set of satisfying initial states. Moreover, for any (partial) solution our algorithm synthesizes witness control strategies to ensure almost-sure satisfaction of the temporal logic specification. We demonstrate our approach on an illustrative case study.

From non-preemptive to preemptive scheduling using synchronization synthesis - Cerny, Pavol; Clarke, Edmund; Henzinger, Thomas A; Radhakrishna, Arjun; Ryzhyk, Leonid; Samanta, Roopsha; Tarrach, Thorsten
We present a computer-aided programming approach to concurrency. The approach allows programmers to program assuming a friendly, non-preemptive scheduler, and our synthesis procedure inserts synchronization to ensure that the final program works even with a preemptive scheduler. The correctness specification is implicit, inferred from the non-preemptive behavior. Let us consider sequences of calls that the program makes to an external interface. The specification requires that any such sequence produced under a preemptive scheduler should be included in the set of such sequences produced under a non-preemptive scheduler. The solution is based on a finitary abstraction, an algorithm for bounded language inclusion modulo an independence relation, and rules for inserting synchronization. We apply the approach to device-driver programming, where the driver threads call the software interface of the device and the API provided by the operating system. Our experiments demonstrate that our synthesis method is precise and efficient, and, since it does not require explicit specifications, is more practical than the conventional approach based on user-provided assertions.

Model checking gene regulatory networks - Giacobbe, Mirco; Guet, Calin C; Gupta, Ashutosh; Henzinger, Thomas A; Paixao, Tiago; Petrov, Tatjana
The behaviour of gene regulatory networks (GRNs) is typically analysed using simulation-based statistical testing-like methods. In this paper, we demonstrate that we can replace this approach by a formal verification-like method that gives higher assurance and scalability. We focus on Wagner’s weighted GRN model with varying weights, which is used in evolutionary biology. In the model, weight parameters represent the gene interaction strength that may change due to genetic mutations. For a property of interest, we synthesise the constraints over the parameter space that represent the set of GRNs satisfying the property. We experimentally show that our parameter synthesis procedure computes the mutational robustness of GRNs –an important problem of interest in evolutionary biology– more efficiently than the classical simulation method. We specify the property in linear temporal logics. We employ symbolic bounded model checking and SMT solving to compute the space of GRNs that satisfy the property, which amounts to synthesizing a set of linear constraints on the weights.

Embryo-lethal phenotypes in early abp1 mutants are due to disruption of the neighboring BSM gene - Michalko, Jaroslav; Dravecka, Marta; Bollenbach, Tobias; Friml, Jirí (F1000 Research)
The Auxin Binding Protein1 (ABP1) has been identified based on its ability to bind auxin with high affinity and studied for a long time as a prime candidate for the extracellular auxin receptor responsible for mediating in particular the fast non-transcriptional auxin responses. However, the contradiction between the embryo-lethal phenotypes of the originally described Arabidopsis T-DNA insertional knock-out alleles (abp1-1 and abp1-1s) and the wild type-like phenotypes of other recently described loss-of-function alleles (abp1-c1 and abp1-TD1) questions the biological importance of ABP1 and relevance of the previous genetic studies. Here we show that there is no hidden copy of the ABP1 gene in the Arabidopsis genome but the embryo-lethal phenotypes of abp1-1 and abp1-1s alleles are very similar to the knock-out phenotypes of the neighboring gene, BELAYA SMERT (BSM). Furthermore, the allelic complementation test between bsm and abp1 alleles shows that the embryo-lethality in the abp1-1 and abp1-1s alleles is caused by the off-target disruption of the BSM locus by the T-DNA insertions. This clarifies the controversy of different phenotypes among published abp1 knock-out alleles and asks for reflections on the developmental role of ABP1.

Evolution of decisions in population games with sequentially searching individuals - Priklopil, Tadeas; Chatterjee, Krishnendu (Games)
In many social situations, individuals endeavor to find the single best possible partner, but are constrained to evaluate the candidates in sequence. Examples include the search for mates, economic partnerships, or any other long-term ties where the choice to interact involves two parties. Surprisingly, however, previous theoretical work on mutual choice problems focuses on finding equilibrium solutions, while ignoring the evolutionary dynamics of decisions. Empirically, this may be of high importance, as some equilibrium solutions can never be reached unless the population undergoes radical changes and a sufficient number of individuals change their decisions simultaneously. To address this question, we apply a mutual choice sequential search problem in an evolutionary game-theoretical model that allows one to find solutions that are favored by evolution. As an example, we study the influence of sequential search on the evolutionary dynamics of cooperation. For this, we focus on the classic snowdrift game and the prisoner’s dilemma game.

Quantifying emergent behavior of autonomous robots - Martius, Georg S; Olbrich, Eckehard (Entropy)
Quantifying behaviors of robots which were generated autonomously from task-independent objective functions is an important prerequisite for objective comparisons of algorithms and movements of animals. The temporal sequence of such a behavior can be considered as a time series and hence complexity measures developed for time series are natural candidates for its quantification. The predictive information and the excess entropy are such complexity measures. They measure the amount of information the past contains about the future and thus quantify the nonrandom structure in the temporal sequence. However, when using these measures for systems with continuous states one has to deal with the fact that their values will depend on the resolution with which the systems states are observed. For deterministic systems both measures will diverge with increasing resolution. We therefore propose a new decomposition of the excess entropy in resolution dependent and resolution independent parts and discuss how they depend on the dimensionality of the dynamics, correlations and the noise level. For the practical estimation we propose to use estimates based on the correlation integral instead of the direct estimation of the mutual information based on next neighbor statistics because the latter allows less control of the scale dependencies. Using our algorithm we are able to show how autonomous learning generates behavior of increasing complexity with increasing learning duration.

Low-dose sevoflurane promoteshippocampal neurogenesis and facilitates the development of dentate gyrus-dependent learning in neonatal rats - Chen, Chong; Wang, Chao; Zhao, Xuan; Zhou, Tao; Xu, Dao; Wang, Zhi; Wang, Ying (ASN Neuro)
Huge body of evidences demonstrated that volatile anesthetics affect the hippocampal neurogenesis and neurocognitive functions, and most of them showed impairment at anesthetic dose. Here, we investigated the effect of low dose (1.8%) sevoflurane on hippocampal neurogenesis and dentate gyrus-dependent learning. Neonatal rats at postnatal day 4 to 6 (P4-6) were treated with 1.8% sevoflurane for 6 hours. Neurogenesis was quantified by bromodeoxyuridine labeling and electrophysiology recording. Four and seven weeks after treatment, the Morris water maze and contextual-fear discrimination learning tests were performed to determine the influence on spatial learning and pattern separation. A 6-hour treatment with 1.8% sevoflurane promoted hippocampal neurogenesis and increased the survival of newborn cells and the proportion of immature granular cells in the dentate gyrus of neonatal rats. Sevoflurane-treated rats performed better during the training days of the Morris water maze test and in contextual-fear discrimination learning test. These results suggest that a subanesthetic dose of sevoflurane promotes hippocampal neurogenesis in neonatal rats and facilitates their performance in dentate gyrus-dependent learning tasks.

Discrete Ricci curvature bounds for Bernoulli-Laplace and random transposition models - Erbar, Matthias; Maas, Jan; Tetali, Prasad (Annales de la faculté des sciences de Toulouse)
We calculate a Ricci curvature lower bound for some classical examples of random walks, namely, a chain on a slice of the n-dimensional discrete cube (the so-called Bernoulli-Laplace model) and the random transposition shuffle of the symmetric group of permutations on n letters.

Counterexample explanation by learning small strategies in Markov decision processes - Brázdil, Tomáš; Chatterjee, Krishnendu; Chmelik, Martin; Fellner, Andreas; Kretinsky, Jan
For deterministic systems, a counterexample to a property can simply be an error trace, whereas counterexamples in probabilistic systems are necessarily more complex. For instance, a set of erroneous traces with a sufficient cumulative probability mass can be used. Since these are too large objects to understand and manipulate, compact representations such as subchains have been considered. In the case of probabilistic systems with non-determinism, the situation is even more complex. While a subchain for a given strategy (or scheduler, resolving non-determinism) is a straightforward choice, we take a different approach. Instead, we focus on the strategy itself, and extract the most important decisions it makes, and present its succinct representation. The key tools we employ to achieve this are (1) introducing a concept of importance of a state w.r.t. the strategy, and (2) learning using decision trees. There are three main consequent advantages of our approach. Firstly, it exploits the quantitative information on states, stressing the more important decisions. Secondly, it leads to a greater variability and degree of freedom in representing the strategies. Thirdly, the representation uses a self-explanatory data structure. In summary, our approach produces more succinct and more explainable strategies, as opposed to e.g. binary decision diagrams. Finally, our experimental results show that we can extract several rules describing the strategy even for very large systems that do not fit in memory, and based on the rules explain the erroneous behaviour.

Experimental part of CAV 2015 publication: Counterexample Explanation by Learning Small Strategies in Markov Decision Processes - Fellner, Andreas
This repository contains the experimental part of the CAV 2015 publication Counterexample Explanation by Learning Small Strategies in Markov Decision Processes. We extended the probabilistic model checker PRISM to represent strategies of Markov Decision Processes as Decision Trees. The archive contains a java executable version of the extended tool (prism_dectree.jar) together with a few examples of the PRISM benchmark library. To execute the program, please have a look at the README.txt, which provides instructions and further information on the archive. The archive contains scripts that (if run often enough) reproduces the data presented in the publication.
Keywords: Markov Decision Process; Decision Tree; Probabilistic Verification; Counterexample Explanation

Bounding Helly numbers via Betti numbers - Goaoc, Xavier; Paták, Pavel; Patakova, Zuzana; Tancer, Martin; Wagner, Uli
We show that very weak topological assumptions are enough to ensure the existence of a Helly-type theorem. More precisely, we show that for any non-negative integers b and d there exists an integer h(b,d) such that the following holds. If F is a finite family of subsets of R^d such that the ith reduced Betti number (with Z_2 coefficients in singular homology) of the intersection of any proper subfamily G of F is at most b for every non-negative integer i less or equal to (d-1)/2, then F has Helly number at most h(b,d). These topological conditions are sharp: not controlling any of these first Betti numbers allow for families with unbounded Helly number. Our proofs combine homological non-embeddability results with a Ramsey-based approach to build, given an arbitrary simplicial complex K, some well-behaved chain map from C_*(K) to C_*(R^d). Both techniques are of independent interest.

Proofs of space - Dziembowski, Stefan; Faust, Sebastian; Kolmogorov, Vladimir; Pietrzak, Krzysztof Z (35th Annual Cryptology Conference)
Proofs of work (PoW) have been suggested by Dwork and Naor (Crypto’92) as protection to a shared resource. The basic idea is to ask the service requestor to dedicate some non-trivial amount of computational work to every request. The original applications included prevention of spam and protection against denial of service attacks. More recently, PoWs have been used to prevent double spending in the Bitcoin digital currency system. In this work, we put forward an alternative concept for PoWs - so-called proofs of space (PoS), where a service requestor must dedicate a significant amount of disk space as opposed to computation. We construct secure PoS schemes in the random oracle model (with one additional mild assumption required for the proof to go through), using graphs with high “pebbling complexity” and Merkle hash-trees. We discuss some applications, including follow-up work where a decentralized digital currency scheme called Spacecoin is constructed that uses PoS (instead of wasteful PoW like in Bitcoin) to prevent double spending. The main technical contribution of this work is the construction of (directed, loop-free) graphs on N vertices with in-degree O(log logN) such that even if one places Θ(N) pebbles on the nodes of the graph, there’s a constant fraction of nodes that needs Θ(N) steps to be pebbled (where in every step one can put a pebble on a node if all its parents have a pebble).

Quantifying the determinants of evolutionary dynamics leading to drug resistance - Chevereau, Guillaume; Dravecka, Marta; Batur, Tugce; Guvenek, Aysegul; Ayhan, Dilay; Toprak, Erdal; Bollenbach, Mark Tobias (PLoS Biology)
The emergence of drug resistant pathogens is a serious public health problem. It is a long-standing goal to predict rates of resistance evolution and design optimal treatment strategies accordingly. To this end, it is crucial to reveal the underlying causes of drug-specific differences in the evolutionary dynamics leading to resistance. However, it remains largely unknown why the rates of resistance evolution via spontaneous mutations and the diversity of mutational paths vary substantially between drugs. Here we comprehensively quantify the distribution of fitness effects (DFE) of mutations, a key determinant of evolutionary dynamics, in the presence of eight antibiotics representing the main modes of action. Using precise high-throughput fitness measurements for genome-wide Escherichia coli gene deletion strains, we find that the width of the DFE varies dramatically between antibiotics and, contrary to conventional wisdom, for some drugs the DFE width is lower than in the absence of stress. We show that this previously underappreciated divergence in DFE width among antibiotics is largely caused by their distinct drug-specific dose-response characteristics. Unlike the DFE, the magnitude of the changes in tolerated drug concentration resulting from genome-wide mutations is similar for most drugs but exceptionally small for the antibiotic nitrofurantoin, i.e., mutations generally have considerably smaller resistance effects for nitrofurantoin than for other drugs. A population genetics model predicts that resistance evolution for drugs with this property is severely limited and confined to reproducible mutational paths. We tested this prediction in laboratory evolution experiments using the “morbidostat”, a device for evolving bacteria in well-controlled drug environments. Nitrofurantoin resistance indeed evolved extremely slowly via reproducible mutations—an almost paradoxical behavior since this drug causes DNA damage and increases the mutation rate. Overall, we identified novel quantitative characteristics of the evolutionary landscape that provide the conceptual foundation for predicting the dynamics of drug resistance evolution.

Molecular and cellular mechanisms of development underlying congenital diseases - Hashimoto, Masakazu; Morita, Hitoshi; Ueno, Naoto (Congenital Anomalies)
In the last several decades, developmental biology has clarified the molecular mechanisms of embryogenesis and organogenesis. In particular, it has demonstrated that the “tool-kit genes” essential for regulating developmental processes are not only highly conserved among species, but are also used as systems at various times and places in an organism to control distinct developmental events. Therefore, mutations in many of these tool-kit genes may cause congenital diseases involving morphological abnormalities. This link between genes and abnormal morphological phenotypes underscores the importance of understanding how cells behave and contribute to morphogenesis as a result of gene function. Recent improvements in live imaging and in quantitative analyses of cellular dynamics will advance our understanding of the cellular pathogenesis of congenital diseases associated with aberrant morphologies. In these studies, it is critical to select an appropriate model organism for the particular phenomenon of interest.
Keywords: Developmental Biology; Embryology; General Medicine; Pediatrics; Perinatology; and Child Health

Auxin and Its Role in Plant Development
Auxin is an important signaling compound in plants and vital for plant development and growth. The present book, Auxin and its Role in Plant Development, provides the reader with detailed and comprehensive insight into the functioning of the molecule on the whole and specifically in plant development. In the first part, the functioning, metabolism and signaling pathways of auxin in plants are explained, the second part depicts the specific role of auxin in plant development and the third part describes the interaction and functioning of the signaling compound upon stimuli of the environment. Each chapter is written by international experts in the respective field and designed for scientists and researchers in plant biology, plant development and cell biology to summarize the recent progress in understanding the role of auxin and suggest future perspectives for auxin research.

Parameterized model checking of token-passing systems - Aminof, Benjamin; Jacobs, Swen; Khalimov, Ayrat; Rubin, Sasha (Verification, Model Checking, and Abstract Interpretation)
We revisit the parameterized model checking problem for token-passing systems and specifications in indexed CTL  ∗ \X. Emerson and Namjoshi (1995, 2003) have shown that parameterized model checking of indexed CTL  ∗ \X in uni-directional token rings can be reduced to checking rings up to some cutoff size. Clarke et al. (2004) have shown a similar result for general topologies and indexed LTL \X, provided processes cannot choose the directions for sending or receiving the token. We unify and substantially extend these results by systematically exploring fragments of indexed CTL  ∗ \X with respect to general topologies. For each fragment we establish whether a cutoff exists, and for some concrete topologies, such as rings, cliques and stars, we infer small cutoffs. Finally, we show that the problem becomes undecidable, and thus no cutoffs exist, if processes are allowed to choose the directions in which they send or from which they receive the token.

Toward the extraction of saddle periodic orbits - Kasten, Jens; Reininghaus, Jan; Reich, Wieland; Scheuermann, Gerik (Topological Methods in Data Analysis and Visualization III)
Saddle periodic orbits are an essential and stable part of the topological skeleton of a 3D vector field. Nevertheless, there is currently no efficient algorithm to robustly extract these features. In this chapter, we present a novel technique to extract saddle periodic orbits. Exploiting the analytic properties of such an orbit, we propose a scalar measure based on the finite-time Lyapunov exponent (FTLE) that indicates its presence. Using persistent homology, we can then extract the robust cycles of this field. These cycles thereby represent the saddle periodic orbits of the given vector field. We discuss the different existing FTLE approximation schemes regarding their applicability to this specific problem and propose an adapted version of FTLE called Normalized Velocity Separation. Finally, we evaluate our method using simple analytic vector field data.

Approximating the minimum cycle mean - Chatterjee, Krishnendu; Henzinger, Monika H; Krinninger, Sebastian; Loitzenbauer, Veronika; Raskin, Michael (Theoretical Computer Science)
We consider directed graphs where each edge is labeled with an integer weight and study the fundamental algorithmic question of computing the value of a cycle with minimum mean weight. Our contributions are twofold: (1) First we show that the algorithmic question is reducible to the problem of a logarithmic number of min-plus matrix multiplications of n×n-matrices, where n is the number of vertices of the graph. (2) Second, when the weights are nonnegative, we present the first (1+ε)-approximation algorithm for the problem and the running time of our algorithm is Õ(nωlog3(nW/ε)/ε),1 where O(nω) is the time required for the classic n×n-matrix multiplication and W is the maximum value of the weights. With an additional O(log(nW/ε)) factor in space a cycle with approximately optimal weight can be computed within the same time bound.

A logic-based framework for verifying consensus algorithms - Dragoi, Cezara; Henzinger, Thomas A; Veith, Helmut; Widder, Josef; Zufferey, Damien
Fault-tolerant distributed algorithms play an important role in ensuring the reliability of many software applications. In this paper we consider distributed algorithms whose computations are organized in rounds. To verify the correctness of such algorithms, we reason about (i) properties (such as invariants) of the state, (ii) the transitions controlled by the algorithm, and (iii) the communication graph. We introduce a logic that addresses these points, and contains set comprehensions with cardinality constraints, function symbols to describe the local states of each process, and a limited form of quantifier alternation to express the verification conditions. We show its use in automating the verification of consensus algorithms. In particular, we give a semi-decision procedure for the unsatisfiability problem of the logic and identify a decidable fragment. We successfully applied our framework to verify the correctness of a variety of consensus algorithms tolerant to both benign faults (message loss, process crashes) and value faults (message corruption).

Probabilistic programming - Gordon, Andrew; Henzinger, Thomas A; Nori, Aditya; Rajamani, Sriram (Proceedings of the on Future of Software Engineering)
Probabilistic programs are usual functional or imperative programs with two added constructs: (1) the ability to draw values at random from distributions, and (2) the ability to condition values of variables in a program via observations. Models from diverse application areas such as computer vision, coding theory, cryptographic protocols, biology and reliability analysis can be written as probabilistic programs. Probabilistic inference is the problem of computing an explicit representation of the probability distribution implicitly specified by a probabilistic program. Depending on the application, the desired output from inference may vary-we may want to estimate the expected value of some function f with respect to the distribution, or the mode of the distribution, or simply a set of samples drawn from the distribution. In this paper, we describe connections this research area called \Probabilistic Programming" has with programming languages and software engineering, and this includes language design, and the static and dynamic analysis of programs. We survey current state of the art and speculate on promising directions for future research.

Evolution of a fungal pathogen towards individual versus social immunity in ants - Stock, Miriam
The co-evolution of hosts and pathogens is characterized by continuous adaptations of both parties. Pathogens of social insects need to adapt towards disease defences at two levels: 1) individual immunity of each colony member consisting of behavioural defence strategies as well as humoral and cellular immune responses and 2) social immunity that is collectively performed by all group members comprising behavioural, physiological and organisational defence strategies. To disentangle the selection pressure on pathogens by the collective versus individual level of disease defence in social insects, we performed an evolution experiment using the Argentine Ant, Linepithema humile, as a host and a mixture of the general insect pathogenic fungus Metarhizium spp. (6 strains) as a pathogen. We allowed pathogen evolution over 10 serial host passages to two different evolution host treatments: (1) only individual host immunity in a single host treatment, and (2) simultaneously acting individual and social immunity in a social host treatment, in which an exposed ant was accompanied by two untreated nestmates. Before starting the pathogen evolution experiment, the 6 Metarhizium spp. strains were characterised concerning conidiospore size killing rates in singly and socially reared ants, their competitiveness under coinfecting conditions and their influence on ant behaviour. We analysed how the ancestral atrain mixture changed in conidiospere size, killing rate and strain composition dependent on host treatment (single or social hosts) during 10 passages and found that killing rate and conidiospere size of the pathogen increased under both evolution regimes, but different depending on host treatment. Testing the evolved strain mixtures that evolved under either the single or social host treatment under both single and social current rearing conditions in a full factorial design experiment revealed that the additional collective defences in insect societies add new selection pressure for their coevolving pathogens that compromise their ability to adapt to its host at the group level. To our knowledge, this is the first study directly measuring the influence of social immunity on pathogen evolution.

On the BCS gap equation for superfluid fermionic gases - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Proceedings of the QMath12 Conference)
We present a rigorous derivation of the BCS gap equation for superfluid fermionic gases with point interactions. Our starting point is the BCS energy functional, whose minimizer we investigate in the limit when the range of the interaction potential goes to zero.

Edit propagation using geometric relationship functions - Guerrero, Paul; Jeschke, Stefan; Wimmer, Michael; Wonka, Peter (ACM Transactions on Graphics)
We propose a method for propagating edit operations in 2D vector graphics, based on geometric relationship functions. These functions quantify the geometric relationship of a point to a polygon, such as the distance to the boundary or the direction to the closest corner vertex. The level sets of the relationship functions describe points with the same relationship to a polygon. For a given query point, we first determine a set of relationships to local features, construct all level sets for these relationships, and accumulate them. The maxima of the resulting distribution are points with similar geometric relationships. We show extensions to handle mirror symmetries, and discuss the use of relationship functions as local coordinate systems. Our method can be applied, for example, to interactive floorplan editing, and it is especially useful for large layouts, where individual edits would be cumbersome. We demonstrate populating 2D layouts with tens to hundreds of objects by propagating relatively few edit operations.

Clustered planarity testing revisited - Fulek, Radoslav; Kynčl, Jan; Malinović, Igor; Pálvölgyi, Dömötör (International Symposium on Graph Drawing)
The Hanani–Tutte theorem is a classical result proved for the first time in the 1930s that characterizes planar graphs as graphs that admit a drawing in the plane in which every pair of edges not sharing a vertex cross an even number of times. We generalize this classical result to clustered graphs with two disjoint clusters, and show that a straightforward extension of our result to flat clustered graphs with three or more disjoint clusters is not possible. We also give a new and short proof for a related result by Di Battista and Frati based on the matroid intersection algorithm.

Constrained Verifiable Random Functions - Fuchsbauer, Georg (SCN 2014)
We extend the notion of verifiable random functions (VRF) to constrained VRFs, which generalize the concept of constrained pseudorandom functions, put forward by Boneh and Waters (Asiacrypt’13), and independently by Kiayias et al. (CCS’13) and Boyle et al. (PKC’14), who call them delegatable PRFs and functional PRFs, respectively. In a standard VRF the secret key sk allows one to evaluate a pseudorandom function at any point of its domain; in addition, it enables computation of a non-interactive proof that the function value was computed correctly. In a constrained VRF from the key sk one can derive constrained keys skS for subsets S of the domain, which allow computation of function values and proofs only at points in S. After formally defining constrained VRFs, we derive instantiations from the multilinear-maps-based constrained PRFs by Boneh and Waters, yielding a VRF with constrained keys for any set that can be decided by a polynomial-size circuit. Our VRFs have the same function values as the Boneh-Waters PRFs and are proved secure under the same hardness assumption, showing that verifiability comes at no cost. Constrained (functional) VRFs were stated as an open problem by Boyle et al.

Generalised interpolation by solving recursion free-horn clauses - Gupta, Ashutosh; Popeea, Corneliu; Rybalchenko, Andrey (Electronic Proceedings in Theoretical Computer Science, EPTCS)
In this paper we present INTERHORN, a solver for recursion-free Horn clauses. The main application domain of INTERHORN lies in solving interpolation problems arising in software verification. We show how a range of interpolation problems, including path, transition, nested, state/transition and well-founded interpolation can be handled directly by INTERHORN. By detailing these interpolation problems and their Horn clause representations, we hope to encourage the emergence of a common back-end interpolation interface useful for diverse verification tools.

Spatio-temporal representations of uncertainty in spiking neural networks - Savin, Cristina; Denève, Sophie
It has been long argued that, because of inherent ambiguity and noise, the brain needs to represent uncertainty in the form of probability distributions. The neural encoding of such distributions remains however highly controversial. Here we present a novel circuit model for representing multidimensional real-valued distributions using a spike based spatio-temporal code. Our model combines the computational advantages of the currently competing models for probabilistic codes and exhibits realistic neural responses along a variety of classic measures. Furthermore, the model highlights the challenges associated with interpreting neural activity in relation to behavioral uncertainty and points to alternative population-level approaches for the experimental validation of distributed representations.

Auxin on the road navigated by cellular PIN polarity - Baster, Pawel; Friml, Jiří (Auxin and Its Role in Plant Development)
The generation of asymmetry, at both cellular and tissue level, is one of the most essential capabilities of all eukaryotic organisms. It mediates basically all multicellular development ranging from embryogenesis and de novo organ formation till responses to various environmental stimuli. In plants, the awe-inspiring number of such processes is regulated by phytohormone auxin and its directional, cell-to-cell transport. The mediators of this transport, PIN auxin transporters, are asymmetrically localized at the plasma membrane, and this polar localization determines the directionality of intercellular auxin flow. Thus, auxin transport contributes crucially to the generation of local auxin gradients or maxima, which instruct given cell to change its developmental program. Here, we introduce and discuss the molecular components and cellular mechanisms regulating the generation and maintenance of cellular PIN polarity, as the general hallmarks of cell polarity in plants.

Topology-preserving watermarking of vector graphics - Huber, Stefan; Held, Martin; Meerwald, Peter; Kwitt, Roland (International Journal of Computational Geometry and Applications)
Watermarking techniques for vector graphics dislocate vertices in order to embed imperceptible, yet detectable, statistical features into the input data. The embedding process may result in a change of the topology of the input data, e.g., by introducing self-intersections, which is undesirable or even disastrous for many applications. In this paper we present a watermarking framework for two-dimensional vector graphics that employs conventional watermarking techniques but still provides the guarantee that the topology of the input data is preserved. The geometric part of this framework computes so-called maximum perturbation regions (MPR) of vertices. We propose two efficient algorithms to compute MPRs based on Voronoi diagrams and constrained triangulations. Furthermore, we present two algorithms to conditionally correct the watermarked data in order to increase the watermark embedding capacity and still guarantee topological correctness. While we focus on the watermarking of input formed by straight-line segments, one of our approaches can also be extended to circular arcs. We conclude the paper by demonstrating and analyzing the applicability of our framework in conjunction with two well-known watermarking techniques.

Bose gases, Bose-Einstein condensation, and the Bogoliubov approximation - Seiringer, Robert (Journal of Mathematical Physics)
We review recent progress towards a rigorous understanding of the Bogoliubov approximation for bosonic quantum many-body systems. We focus, in particular, on the excitation spectrum of a Bose gas in the mean-field (Hartree) limit. A list of open problems will be discussed at the end.

Introduction - Jakšić, Vojkan; Pillet, Claude; Seiringer, Robert (Journal of Mathematical Physics)

Movement templates for learning of hitting and batting - Muelling, Katharina; Kroemer, Oliver; Lampert, Christoph; Schölkopf, Bernhard (Learning Motor Skills)
Hitting and batting tasks, such as tennis forehands, ping-pong strokes, or baseball batting, depend on predictions where the ball can be intercepted and how it can properly be returned to the opponent. These predictions get more accurate over time, hence the behaviors need to be continuously modified. As a result, movement templates with a learned global shape need to be adapted during the execution so that the racket reaches a target position and velocity that will return the ball over to the other side of the net or court. It requires altering learned movements to hit a varying target with the necessary velocity at a specific instant in time. Such a task cannot be incorporated straightforwardly in most movement representations suitable for learning. For example, the standard formulation of the dynamical system based motor primitives (introduced by Ijspeert et al (2002b)) does not satisfy this property despite their flexibility which has allowed learning tasks ranging from locomotion to kendama. In order to fulfill this requirement, we reformulate the Ijspeert framework to incorporate the possibility of specifying a desired hitting point and a desired hitting velocity while maintaining all advantages of the original formulation.We show that the proposed movement template formulation works well in two scenarios, i.e., for hitting a ball on a string with a table tennis racket at a specified velocity and for returning balls launched by a ball gun successfully over the net using forehand movements.

Mutational studies on resurrected ancestral proteins reveal conservation of site-specific amino acid preferences throughout evolutionary history - Risso, Valeria; Manssour Triedo, Fadia; Delgado Delgado, Asuncion; Arco, Rocio; Barroso Deljesús, Alicia; Inglés Prieto, Álvaro; Godoy Ruiz, Raquel; Gavira, Josè; Gaucher, Eric; Ibarra Molero, Beatriz; Sánchez Ruiz, Jose (Molecular Biology and Evolution)
Local protein interactions ("molecular context" effects) dictate amino acid replacements and can be described in terms of site-specific, energetic preferences for any different amino acid. It has been recently debated whether these preferences remain approximately constant during evolution or whether, due to coevolution of sites, they change strongly. Such research highlights an unresolved and fundamental issue with far-reaching implications for phylogenetic analysis and molecular evolution modeling. Here, we take advantage of the recent availability of phenotypically supported laboratory resurrections of Precambrian thioredoxins and β-lactamases to experimentally address the change of site-specific amino acid preferences over long geological timescales. Extensive mutational analyses support the notion that evolutionary adjustment to a new amino acid may occur, but to a large extent this is insufficient to erase the primitive preference for amino acid replacements. Generally, site-specific amino acid preferences appear to remain conserved throughout evolutionary history despite local sequence divergence. We show such preference conservation to be readily understandable in molecular terms and we provide crystallographic evidence for an intriguing structural-switch mechanism: Energetic preference for an ancestral amino acid in a modern protein can be linked to reorganization upon mutation to the ancestral local structure around the mutated site. Finally, we point out that site-specific preference conservation naturally leads to one plausible evolutionary explanation for the existence of intragenic global suppressor mutations.

On the geometric ramsey number of outerplanar graphs - Cibulka, Josef; Gao, Pu; Krcál, Marek; Valla, Tomáš; Valtr, Pavel (Discrete & Computational Geometry)
We prove polynomial upper bounds of geometric Ramsey numbers of pathwidth-2 outerplanar triangulations in both convex and general cases. We also prove that the geometric Ramsey numbers of the ladder graph on 2n vertices are bounded by O(n3) and O(n10), in the convex and general case, respectively. We then apply similar methods to prove an (Formula presented.) upper bound on the Ramsey number of a path with n ordered vertices.

Partial shape matching using transformation parameter similarity - Guerrero, Paul; Auzinger, Thomas; Wimmer, Michael; Jeschke, Stefan (Computer Graphics Forum)
In this paper, we present a method for non-rigid, partial shape matching in vector graphics. Given a user-specified query region in a 2D shape, similar regions are found, even if they are non-linearly distorted. Furthermore, a non-linear mapping is established between the query regions and these matches, which allows the automatic transfer of editing operations such as texturing. This is achieved by a two-step approach. First, pointwise correspondences between the query region and the whole shape are established. The transformation parameters of these correspondences are registered in an appropriate transformation space. For transformations between similar regions, these parameters form surfaces in transformation space, which are extracted in the second step of our method. The extracted regions may be related to the query region by a non-rigid transform, enabling non-rigid shape matching. In this paper, we present a method for non-rigid, partial shape matching in vector graphics. Given a user-specified query region in a 2D shape, similar regions are found, even if they are non-linearly distorted. Furthermore, a non-linear mapping is established between the query regions and these matches, which allows the automatic transfer of editing operations such as texturing. This is achieved by a two-step approach. First, pointwise correspondences between the query region and the whole shape are established. The transformation parameters of these correspondences are registered in an appropriate transformation space. For transformations between similar regions, these parameters form surfaces in transformation space, which are extracted in the second step of our method. The extracted regions may be related to the query region by a non-rigid transform, enabling non-rigid shape matching.

An auxin-mediated shift toward growth isotropy promotes organ formation at the shoot meristem in Arabidopsis - Sassi, Massimiliano; Ali, Olivier; Boudon, Frédéric; Cloarec, Gladys; Abad, Ursula; Cellier, Coralie; Chen, Xu; Gilles, Benjamin; Milani, Pascale; Friml, Jirí; Vernoux, Teva; Godin, Christophe; et al. (Current Biology)
To control morphogenesis, molecular regulatory networks have to interfere with the mechanical properties of the individual cells of developing organs and tissues, but how this is achieved is not well known. We study this issue here in the shoot meristem of higher plants, a group of undifferentiated cells where complex changes in growth rates and directions lead to the continuous formation of new organs [1, 2]. Here, we show that the plant hormone auxin plays an important role in this process via a dual, local effect on the extracellular matrix, the cell wall, which determines cell shape. Our study reveals that auxin not only causes a limited reduction in wall stiffness but also directly interferes with wall anisotropy via the regulation of cortical microtubule dynamics. We further show that to induce growth isotropy and organ outgrowth, auxin somehow interferes with the cortical microtubule-ordering activity of a network of proteins, including AUXIN BINDING PROTEIN 1 and KATANIN 1. Numerical simulations further indicate that the induced isotropy is sufficient to amplify the effects of the relatively minor changes in wall stiffness to promote organogenesis and the establishment of new growth axes in a robust manner.

Game theoretic secure localization in wireless sensor networks - Jha, Susmit; Tripakis, Stavros; Seshia, Sanjit; Chatterjee, Krishnendu
Wireless sensor networks (WSNs) composed of low-power, low-cost sensor nodes are expected to form the backbone of future intelligent networks for a broad range of civil, industrial and military applications. These sensor nodes are often deployed through random spreading, and function in dynamic environments. Many applications of WSNs such as pollution tracking, forest fire detection, and military surveillance require knowledge of the location of constituent nodes. But the use of technologies such as GPS on all nodes is prohibitive due to power and cost constraints. So, the sensor nodes need to autonomously determine their locations. Most localization techniques use anchor nodes with known locations to determine the position of remaining nodes. Localization techniques have two conflicting requirements. On one hand, an ideal localization technique should be computationally simple and on the other hand, it must be resistant to attacks that compromise anchor nodes. In this paper, we propose a computationally light-weight game theoretic secure localization technique and demonstrate its effectiveness in comparison to existing techniques.

Inhibition of cell expansion by rapid ABP1-mediated auxin effect on microtubules - Chen, Xu; Grandont, Laurie; Li, Hongjiang; Hauschild, Robert; Paque, Sébastien; Abuzeineh, Anas; Rakusova, Hana; Benková, Eva; Perrot Rechenmann, Catherine; Friml, Jirí (Nature)
The prominent and evolutionarily ancient role of the plant hormone auxin is the regulation of cell expansion. Cell expansion requires ordered arrangement of the cytoskeleton but molecular mechanisms underlying its regulation by signalling molecules including auxin are unknown. Here we show in the model plant Arabidopsis thaliana that in elongating cells exogenous application of auxin or redistribution of endogenous auxin induces very rapid microtubule re-orientation from transverse to longitudinal, coherent with the inhibition of cell expansion. This fast auxin effect requires auxin binding protein 1 (ABP1) and involves a contribution of downstream signalling components such as ROP6 GTPase, ROP-interactive protein RIC1 and the microtubule-severing protein katanin. These components are required for rapid auxin-and ABP1-mediated re-orientation of microtubules to regulate cell elongation in roots and dark-grown hypocotyls as well as asymmetric growth during gravitropic responses.

Suraq - a controller synthesis tool using uninterpreted functions - Hofferek, Georg; Gupta, Ashutosh (HVC 2014)
Boolean controllers for systems with complex datapaths are often very difficult to implement correctly, in particular when concurrency is involved. Yet, in many instances it is easy to formally specify correctness. For example, the specification for the controller of a pipelined processor only has to state that the pipelined processor gives the same results as a non-pipelined reference design. This makes such controllers a good target for automated synthesis. However, an efficient abstraction for the complex datapath elements is needed, as a bit-precise description is often infeasible. We present Suraq, the first controller synthesis tool which uses uninterpreted functions for the abstraction. Quantified firstorder formulas (with specific quantifier structure) serve as the specification language from which Suraq synthesizes Boolean controllers. Suraq transforms the specification into an unsatisfiable SMT formula, and uses Craig interpolation to compute its results. Using Suraq, we were able to synthesize a controller (consisting of two Boolean signals) for a five-stage pipelined DLX processor in roughly one hour and 15 minutes.

Extensional crisis and proving identity - Gupta, Ashutosh; Kovács, Laura; Kragl, Bernhard; Voronkov, Andrei (ATVA 2014)
Extensionality axioms are common when reasoning about data collections, such as arrays and functions in program analysis, or sets in mathematics. An extensionality axiom asserts that two collections are equal if they consist of the same elements at the same indices. Using extensionality is often required to show that two collections are equal. A typical example is the set theory theorem (∀x)(∀y)x∪y = y ∪x. Interestingly, while humans have no problem with proving such set identities using extensionality, they are very hard for superposition theorem provers because of the calculi they use. In this paper we show how addition of a new inference rule, called extensionality resolution, allows first-order theorem provers to easily solve problems no modern first-order theorem prover can solve. We illustrate this by running the VAMPIRE theorem prover with extensionality resolution on a number of set theory and array problems. Extensionality resolution helps VAMPIRE to solve problems from the TPTP library of first-order problems that were never solved before by any prover.

Lipschitz robustness of finite-state transducers - Henzinger, Thomas A; Otop, Jan; Samanta, Roopsha (Leibniz International Proceedings in Informatics, LIPIcs)
We investigate the problem of checking if a finite-state transducer is robust to uncertainty in its input. Our notion of robustness is based on the analytic notion of Lipschitz continuity - a transducer is K-(Lipschitz) robust if the perturbation in its output is at most K times the perturbation in its input. We quantify input and output perturbation using similarity functions. We show that K-robustness is undecidable even for deterministic transducers. We identify a class of functional transducers, which admits a polynomial time automata-theoretic decision procedure for K-robustness. This class includes Mealy machines and functional letter-to-letter transducers. We also study K-robustness of nondeterministic transducers. Since a nondeterministic transducer generates a set of output words for each input word, we quantify output perturbation using setsimilarity functions. We show that K-robustness of nondeterministic transducers is undecidable, even for letter-to-letter transducers. We identify a class of set-similarity functions which admit decidable K-robustness of letter-to-letter transducers.

Cost-aware automatic program repair - Samanta, Roopsha; Olivo, Oswaldo; Allen, Emerson
We present a formal framework for repairing infinite-state, imperative, sequential programs, with (possibly recursive) procedures and multiple assertions; the framework can generate repaired programs by modifying the original erroneous program in multiple program locations, and can ensure the readability of the repaired program using user-defined expression templates; the framework also generates a set of inductive assertions that serve as a proof of correctness of the repaired program. As a step toward integrating programmer intent and intuition in automated program repair, we present a cost-aware formulation - given a cost function associated with permissible statement modifications, the goal is to ensure that the total program modification cost does not exceed a given repair budget. As part of our predicate abstractionbased solution framework, we present a sound and complete algorithm for repair of Boolean programs. We have developed a prototype tool based on SMT solving and used it successfully to repair diverse errors in benchmark C programs.

Functionals on triangulations of delaunay sets - Dolbilin, Nikolai; Edelsbrunner, Herbert; Glazyrin, Alexey; Musin, Oleg (Moscow Mathematical Journal)
We study densities of functionals over uniformly bounded triangulations of a Delaunay set of vertices, and prove that the minimum is attained for the Delaunay triangulation if this is the case for finite sets.

Physiology: Relax and come in - Sixt, Michael K; Vaahtomeri, Kari (Nature)
During inflammation, lymph nodes swell with an influx of immune cells. New findings identify a signalling pathway that induces relaxation in the contractile cells that give structure to these organs.

Variance predicts salience in central sensory processing - Hermundstad, Ann; Briguglio, John; Conte, Mary; Victor, Jonathan; Balasubramanian, Vijay; Tkacik, Gasper (eLife)
Information processing in the sensory periphery is shaped by natural stimulus statistics. In the periphery, a transmission bottleneck constrains performance; thus efficient coding implies that natural signal components with a predictably wider range should be compressed. In a different regime—when sampling limitations constrain performance—efficient coding implies that more resources should be allocated to informative features that are more variable. We propose that this regime is relevant for sensory cortex when it extracts complex features from limited numbers of sensory samples. To test this prediction, we use central visual processing as a model: we show that visual sensitivity for local multi-point spatial correlations, described by dozens of independently-measured parameters, can be quantitatively predicted from the structure of natural images. This suggests that efficient coding applies centrally, where it extends to higher-order sensory features and operates in a regime in which sensitivity increases with feature variability.

Sequential effects in continued visual search: Using fixation-related potentials to compare distractor processing before and after target detection - Körner, Christof; Braunstein, Verena; Stangl, Matthias; Schlögl, Alois; Neuper, Christa; Ischebeck, Anja (Psychophysiology)
To search for a target in a complex environment is an everyday behavior that ends with finding the target. When we search for two identical targets, however, we must continue the search after finding the first target and memorize its location. We used fixation-related potentials to investigate the neural correlates of different stages of the search, that is, before and after finding the first target. Having found the first target influenced subsequent distractor processing. Compared to distractor fixations before the first target fixation, a negative shift was observed for three subsequent distractor fixations. These results suggest that processing a target in continued search modulates the brain's response, either transiently by reflecting temporary working memory processes or permanently by reflecting working memory retention.

Y-linked Mendelian inheritance of giant and dwarf male morphs in shell-brooding cichlids - Ocana, Sabine; Meidl, Patrick; Bonfils, Danielle; Taborsky, Michael (Proceedings of the Royal Society of London Series B Biological Sciences)
Behavioural variation among conspecifics is typically contingent on individual state or environmental conditions. Sex-specific genetic polymorphisms are enigmatic because they lack conditionality, and genes causing adaptive trait variation in one sex may reduce Darwinian fitness in the other. One way to avoid such genetic antagonism is to control sex-specific traits by inheritance via sex chromosomes. Here, controlled laboratory crossings suggest that in snail-brooding cichlid fish a single locus, two-allele polymorphism located on a sex-linked chromosome of heterogametic males generates an extreme reproductive dimorphism. Both natural and sexual selection are responsible for exceptionally large body size of bourgeois males, creating a niche for a miniature male phenotype to evolve. This extreme intrasexual dimorphism results from selection on opposite size thresholds caused by a single ecological factor, empty snail shells used as breeding substrate. Paternity analyses reveal that in the field parasitic dwarf males sire the majority of offspring in direct sperm competition with large nest owners exceeding their size more than 40 times. Apparently, use of empty snail shells as breeding substrate and single locus sex-linked inheritance of growth are the major ecological and genetic mechanisms responsible for the extreme intrasexual diversity observed in Lamprologus callipterus.

Theoretical tests of the mechanical protection strategy in protein nanomechanics - Chwastyk, Mateusz; Galera Prat, Albert; Sikora, Mateusz K; Gómez Sicilia, Àngel; Carrión Vázquez, Mariano; Cieplak, Marek (Proteins: Structure, Function and Bioinformatics)
We provide theoretical tests of a novel experimental technique to determine mechanostability of proteins based on stretching a mechanically protected protein by single-molecule force spectroscopy. This technique involves stretching a homogeneous or heterogeneous chain of reference proteins (single-molecule markers) in which one of them acts as host to the guest protein under study. The guest protein is grafted into the host through genetic engineering. It is expected that unraveling of the host precedes the unraveling of the guest removing ambiguities in the reading of the force-extension patterns of the guest protein. We study examples of such systems within a coarse-grained structure-based model. We consider systems with various ratios of mechanostability for the host and guest molecules and compare them to experimental results involving cohesin I as the guest molecule. For a comparison, we also study the force-displacement patterns in proteins that are linked in a serial fashion. We find that the mechanostability of the guest is similar to that of the isolated or serially linked protein. We also demonstrate that the ideal configuration of this strategy would be one in which the host is much more mechanostable than the single-molecule markers. We finally show that it is troublesome to use the highly stable cystine knot proteins as a host to graft a guest in stretching studies because this would involve a cleaving procedure.

Novel putative driver gene mutations in chronic lymphocytic leukemia (CLL): results from a combined analysis of whole exome sequencing of 262 primary CLL aamples - Landau, Dan; Stewart, Chip; Reiter, Johannes; Lawrence, Michael; Sougnez, Carrie; Brown, Jennifer; Lopez Guillermo, Armando; Gabriel, Stacey; Lander, Eric; Neuberg, Donna; López Otín, Carlos; Campo, Elias; et al. (Blood)
Unbiased high-throughput massively parallel sequencing methods have transformed the process of discovery of novel putative driver gene mutations in cancer. In chronic lymphocytic leukemia (CLL), these methods have yielded several unexpected findings, including the driver genes SF3B1, NOTCH1 and POT1. Recent analysis, utilizing down-sampling of existing datasets, has shown that the discovery process of putative drivers is far from complete across cancer. In CLL, while driver gene mutations affecting >10% of patients were efficiently discovered with previously published CLL cohorts of up to 160 samples subjected to whole exome sequencing (WES), this sample size has only 0.78 power to detect drivers affecting 5% of patients, and only 0.12 power for drivers affecting 2% of patients. These calculations emphasize the need to apply unbiased WES to larger patient cohorts.

Translation-invariant quasi-free states for fermionic systems and the BCS approximation - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Reviews in Mathematical Physics)
We study translation-invariant quasi-free states for a system of fermions with two-particle interactions. The associated energy functional is similar to the BCS functional but also includes direct and exchange energies. We show that for suitable short-range interactions, these latter terms only lead to a renormalization of the chemical potential, with the usual properties of the BCS functional left unchanged. Our analysis thus represents a rigorous justification of part of the BCS approximation. We give bounds on the critical temperature below which the system displays superfluidity.

Functional and bioinformatics analysis of two Campylobacter jejuni homologs of the thiol-disulfide oxidoreductase, DsbA - Grabowska, Anna; Wywiał, Ewa; Dunin Horkawicz, Stanislaw; Łasica, Anna; Wösten, Marc; Nagy-Staron, Anna A; Godlewska, Renata; Bocian Ostrzycka, Katarzyna; Pieńkowska, Katarzyna; Łaniewski, Paweł; Bujnicki, Janusz; Van Putten, Jos; et al. (PLoS One)
Background: Bacterial Dsb enzymes are involved in the oxidative folding of many proteins, through the formation of disulfide bonds between their cysteine residues. The Dsb protein network has been well characterized in cells of the model microorganism Escherichia coli. To gain insight into the functioning of the Dsb system in epsilon-Proteobacteria, where it plays an important role in the colonization process, we studied two homologs of the main Escherichia coli Dsb oxidase (EcDsbA) that are present in the cells of the enteric pathogen Campylobacter jejuni, the most frequently reported bacterial cause of human enteritis in the world. Methods and Results: Phylogenetic analysis suggests the horizontal transfer of the epsilon-Proteobacterial DsbAs from a common ancestor to gamma-Proteobacteria, which then gave rise to the DsbL lineage. Phenotype and enzymatic assays suggest that the two C. jejuni DsbAs play different roles in bacterial cells and have divergent substrate spectra. CjDsbA1 is essential for the motility and autoagglutination phenotypes, while CjDsbA2 has no impact on those processes. CjDsbA1 plays a critical role in the oxidative folding that ensures the activity of alkaline phosphatase CjPhoX, whereas CjDsbA2 is crucial for the activity of arylsulfotransferase CjAstA, encoded within the dsbA2-dsbB-astA operon. Conclusions: Our results show that CjDsbA1 is the primary thiol-oxidoreductase affecting life processes associated with bacterial spread and host colonization, as well as ensuring the oxidative folding of particular protein substrates. In contrast, CjDsbA2 activity does not affect the same processes and so far its oxidative folding activity has been demonstrated for one substrate, arylsulfotransferase CjAstA. The results suggest the cooperation between CjDsbA2 and CjDsbB. In the case of the CjDsbA1, this cooperation is not exclusive and there is probably another protein to be identified in C. jejuni cells that acts to re-oxidize CjDsbA1. Altogether the data presented here constitute the considerable insight to the Epsilonproteobacterial Dsb systems, which have been poorly understood so far.

Functional deficiency of MHC class i enhances LTP and abolishes LTD in the nucleus accumbens of mice - Edamura, Mitsuhiro; Murakami, Gen; Meng, Hongrui; Itakura, Makoto; Shigemoto, Ryuichi; Fukuda, Atsuo; Nakahara, Daiichiro (PLoS One)
Major histocompatibility complex class I (MHCI) molecules were recently identified as novel regulators of synaptic plasticity. These molecules are expressed in various brain areas, especially in regions undergoing activity-dependent synaptic plasticity, but their role in the nucleus accumbens (NAc) is unknown. In this study, we investigated the effects of genetic disruption of MHCI function, through deletion of β2-microblobulin, which causes lack of cell surface expression of MHCI. First, we confirmed that MHCI molecules are expressed in the NAc core in wild-type mice. Second, we performed electrophysiological recordings with NAc core slices from wild-type and β2-microglobulin knock-out mice lacking cell surface expression of MHCI. We found that low frequency stimulation induced long-term depression in wild-type but not knock-out mice, whereas high frequency stimulation induced long-term potentiation in both genotypes, with a larger magnitude in knock-out mice. Furthermore, we demonstrated that knock-out mice showed more persistent behavioral sensitization to cocaine, which is a NAc-related behavior. Using this model, we analyzed the density of total AMPA receptors and their subunits GluR1 and GluR2 in the NAc core, by SDS-digested freeze-fracture replica labeling. After repeated cocaine exposure, the density of GluR1 was increased, but there was no change in total AMPA receptors and GluR2 levels in wildtype mice. In contrast, following repeated cocaine exposure, increased densities of total AMPA receptors, GluR1 and GluR2 were observed in knock-out mice. These results indicate that functional deficiency of MHCI enhances synaptic potentiation, induced by electrical and pharmacological stimulation.

SAC phosphoinositide phosphatases at the tonoplast mediate vacuolar function in Arabidopsis - Nováková, Petra; Hirsch, Sibylle; Feraru, Elena; Tejos, Ricardo; Van Wijk, Ringo; Viaene, Tom; Heilmann, Mareike; Lerche, Jennifer; De Rycke, Riet; Feraru, Mugurel; Grones, Peter; Van Montagu, Marc; et al. (PNAS)
Phosphatidylinositol (PtdIns) is a structural phospholipid that can be phosphorylated into various lipid signaling molecules, designated polyphosphoinositides (PPIs). The reversible phosphorylation of PPIs on the 3, 4, or 5 position of inositol is performed by a set of organelle-specific kinases and phosphatases, and the characteristic head groups make these molecules ideal for regulating biological processes in time and space. In yeast and mammals, PtdIns3P and PtdIns(3,5)P2 play crucial roles in trafficking toward the lytic compartments, whereas the role in plants is not yet fully understood. Here we identified the role of a land plant-specific subgroup of PPI phosphatases, the suppressor of actin 2 (SAC2) to SAC5, during vacuolar trafficking and morphogenesis in Arabidopsis thaliana. SAC2-SAC5 localize to the tonoplast along with PtdIns3P, the presumable product of their activity. In SAC gain- and loss-of-function mutants, the levels of PtdIns monophosphates and bisphosphates were changed, with opposite effects on the morphology of storage and lytic vacuoles, and the trafficking toward the vacuoles was defective. Moreover, multiple sac knockout mutants had an increased number of smaller storage and lytic vacuoles, whereas extralarge vacuoles were observed in the overexpression lines, correlating with various growth and developmental defects. The fragmented vacuolar phenotype of sac mutants could be mimicked by treating wild-type seedlings with PtdIns(3,5)P2, corroborating that this PPI is important for vacuole morphology. Taken together, these results provide evidence that PPIs, together with their metabolic enzymes SAC2-SAC5, are crucial for vacuolar trafficking and for vacuolar morphology and function in plants.

Mathematical model of alternative mechanism of telomere length maintenance - Kollár, Richard; Bod'ová, Katarína; Nosek, Jozef; Tomáška, Ľubomír (Physical Review E Statistical Nonlinear and Soft Matter Physics)
Biopolymer length regulation is a complex process that involves a large number of biological, chemical, and physical subprocesses acting simultaneously across multiple spatial and temporal scales. An illustrative example important for genomic stability is the length regulation of telomeres - nucleoprotein structures at the ends of linear chromosomes consisting of tandemly repeated DNA sequences and a specialized set of proteins. Maintenance of telomeres is often facilitated by the enzyme telomerase but, particularly in telomerase-free systems, the maintenance of chromosomal termini depends on alternative lengthening of telomeres (ALT) mechanisms mediated by recombination. Various linear and circular DNA structures were identified to participate in ALT, however, dynamics of the whole process is still poorly understood. We propose a chemical kinetics model of ALT with kinetic rates systematically derived from the biophysics of DNA diffusion and looping. The reaction system is reduced to a coagulation-fragmentation system by quasi-steady-state approximation. The detailed treatment of kinetic rates yields explicit formulas for expected size distributions of telomeres that demonstrate the key role played by the J factor, a quantitative measure of bending of polymers. The results are in agreement with experimental data and point out interesting phenomena: an appearance of very long telomeric circles if the total telomere density exceeds a critical value (excess mass) and a nonlinear response of the telomere size distributions to the amount of telomeric DNA in the system. The results can be of general importance for understanding dynamics of telomeres in telomerase-independent systems as this mode of telomere maintenance is similar to the situation in tumor cells lacking telomerase activity. Furthermore, due to its universality, the model may also serve as a prototype of an interaction between linear and circular DNA structures in various settings.

Insights into the localization and function of the membrane trafficking regulator GNOM ARF-GEF at the Golgi apparatus in Arabidopsis - Naramoto, Satoshi; Otegui, Marisa; Kutsuna, Natsumaro; De Rycke, Riet; Dainobu, Tomoko; Karampelias, Michael; Fujimoto, Masaru; Feraru, Elena; Miki, Daisuke; Fukuda, Hiroo; Nakano, Akihiko; Friml, Jirí (Plant Cell)
GNOM is one of the most characterized membrane trafficking regulators in plants, with crucial roles in development. GNOM encodes an ARF-guanine nucleotide exchange factor (ARF-GEF) that activates small GTPases of the ARF (ADP ribosylation factor) class to mediate vesicle budding at endomembranes. The crucial role of GNOM in recycling of PIN auxin transporters and other proteins to the plasma membrane was identified in studies using the ARF-GEF inhibitor brefeldin A (BFA). GNOM, the most prominent regulator of recycling in plants, has been proposed to act and localize at so far elusive recycling endosomes. Here, we report the GNOM localization in context of its cellular function in Arabidopsis thaliana. State-of-the-art imaging, pharmacological interference, and ultrastructure analysis show that GNOM predominantly localizes to Golgi apparatus. Super-resolution confocal live imaging microscopy identified GNOM and its closest homolog GNOM-like 1 at distinct subdomains on Golgi cisternae. Short-term BFA treatment stabilizes GNOM at the Golgi apparatus, whereas prolonged exposures results in GNOM translocation to trans-Golgi network (TGN)/early endosomes (EEs). Malformed TGN/EE in gnom mutants suggests a role for GNOM in maintaining TGN/EE function. Our results redefine the subcellular action of GNOM and reevaluate the identity and function of recycling endosomes in plants.

Par3-mInsc and Gα i3 cooperate to promote oriented epidermal cell divisions through LGN - Williams, Scott; Ratliff, Lyndsay; Postiglione, Maria P; Knoblich, Juergen; Fuchs, Elaine (Nature Cell Biology)
Asymmetric cell divisions allow stem cells to balance proliferation and differentiation. During embryogenesis, murine epidermis expands rapidly from a single layer of unspecified basal layer progenitors to a stratified, differentiated epithelium. Morphogenesis involves perpendicular (asymmetric) divisions and the spindle orientation protein LGN, but little is known about how the apical localization of LGN is regulated. Here, we combine conventional genetics and lentiviral-mediated in vivo RNAi to explore the functions of the LGN-interacting proteins Par3, mInsc and Gα i3. Whereas loss of each gene alone leads to randomized division angles, combined loss of Gnai3 and mInsc causes a phenotype of mostly planar divisions, akin to loss of LGN. These findings lend experimental support for the hitherto untested model that Par3-mInsc and Gα i3 act cooperatively to polarize LGN and promote perpendicular divisions. Finally, we uncover a developmental switch between delamination-driven early stratification and spindle-orientation-dependent differentiation that occurs around E15, revealing a two-step mechanism underlying epidermal maturation.

Ultrafast action potentials mediate kilohertz signaling at a central synapse - Ritzau Jost, Andreas; Delvendahl, Igor; Rings, Annika; Byczkowicz, Niklas; Harada, Harumi; Shigemoto, Ryuichi; Hirrlinger, Johannes; Eilers, Jens; Hallermann, Stefan (Neuron)
Fast synaptic transmission is important for rapid information processing. To explore the maximal rate of neuronal signaling and to analyze the presynaptic mechanisms, we focused on the input layer of the cerebellar cortex, where exceptionally high action potential (AP) frequencies have been reported invivo. With paired recordings between presynaptic cerebellar mossy fiber boutons and postsynaptic granule cells, we demonstrate reliable neurotransmission upto ~1 kHz. Presynaptic APs are ultrafast, with ~100μs half-duration. Both Kv1 and Kv3 potassium channels mediate the fast repolarization, rapidly inactivating sodium channels ensure metabolic efficiency, and little AP broadening occurs during bursts of up to 1.5 kHz. Presynaptic Cav2.1 (P/Q-type) calcium channels open efficiently during ultrafast APs. Furthermore, a subset of synaptic vesicles is tightly coupled to Ca2+ channels, and vesicles are rapidly recruited to the release site. These data reveal mechanisms of presynaptic AP generation and transmitter release underlying neuronal kHz signaling.

Large-scale point-cloud visualization through localized textured surface reconstruction - Arikan, Murat; Preiner, Reinhold; Scheiblauer, Claus; Jeschke, Stefan; Wimmer, Michael (IEEE Transactions on Visualization and Computer Graphics)
In this paper, we introduce a novel scene representation for the visualization of large-scale point clouds accompanied by a set of high-resolution photographs. Many real-world applications deal with very densely sampled point-cloud data, which are augmented with photographs that often reveal lighting variations and inaccuracies in registration. Consequently, the high-quality representation of the captured data, i.e., both point clouds and photographs together, is a challenging and time-consuming task. We propose a two-phase approach, in which the first (preprocessing) phase generates multiple overlapping surface patches and handles the problem of seamless texture generation locally for each patch. The second phase stitches these patches at render-time to produce a high-quality visualization of the data. As a result of the proposed localization of the global texturing problem, our algorithm is more than an order of magnitude faster than equivalent mesh-based texturing techniques. Furthermore, since our preprocessing phase requires only a minor fraction of the whole data set at once, we provide maximum flexibility when dealing with growing data sets.

Selection from parasites favours immunogenetic diversity but not divergence among locally adapted host populations - Tobler, Michael; Plath, Martin; Riesch, Rüdiger; Schlupp, Ingo; Grasse, Anna V; Munimanda, Gopi; Setzer, C; Penn, Dustin; Moodley, Yoshan (Journal of Evolutionary Biology)
The unprecedented polymorphism in the major histocompatibility complex (MHC) genes is thought to be maintained by balancing selection from parasites. However, do parasites also drive divergence at MHC loci between host populations, or do the effects of balancing selection maintain similarities among populations? We examined MHC variation in populations of the livebearing fish Poecilia mexicana and characterized their parasite communities. Poecilia mexicana populations in the Cueva del Azufre system are locally adapted to darkness and the presence of toxic hydrogen sulphide, representing highly divergent ecotypes or incipient species. Parasite communities differed significantly across populations, and populations with higher parasite loads had higher levels of diversity at class II MHC genes. However, despite different parasite communities, marked divergence in adaptive traits and in neutral genetic markers, we found MHC alleles to be remarkably similar among host populations. Our findings indicate that balancing selection from parasites maintains immunogenetic diversity of hosts, but this process does not promote MHC divergence in this system. On the contrary, we suggest that balancing selection on immunogenetic loci may outweigh divergent selection causing divergence, thereby hindering host divergence and speciation. Our findings support the hypothesis that balancing selection maintains MHC similarities among lineages during and after speciation (trans-species evolution).

Growth rates made easy - Hall, Barry; Acar, Hande; Nandipati, Anna; Barlow, Miriam (Molecular Biology and Evolution)
In the 1960s-1980s, determination of bacterial growth rates was an important tool in microbial genetics, biochemistry, molecular biology, and microbial physiology. The exciting technical developments of the 1990s and the 2000s eclipsed that tool; as a result, many investigators today lack experience with growth rate measurements. Recently, investigators in a number of areas have started to use measurements of bacterial growth rates for a variety of purposes. Those measurements have been greatly facilitated by the availability of microwell plate readers that permit the simultaneous measurements on up to 384 different cultures. Only the exponential (logarithmic) portions of the resulting growth curves are useful for determining growth rates, and manual determination of that portion and calculation of growth rates can be tedious for high-throughput purposes. Here, we introduce the program GrowthRates that uses plate reader output files to automatically determine the exponential portion of the curve and to automatically calculate the growth rate, the maximum culture density, and the duration of the growth lag phase. GrowthRates is freely available for Macintosh, Windows, and Linux.We discuss the effects of culture volume, the classical bacterial growth curve, and the differences between determinations in rich media and minimal (mineral salts) media. This protocol covers calibration of the plate reader, growth of culture inocula for both rich and minimal media, and experimental setup. As a guide to reliability, we report typical day-to-day variation in growth rates and variation within experiments with respect to position of wells within the plates.

WOX5-IAA17 feedback circuit-mediated cellular auxin response is crucial for the patterning of root stem cell niches in arabidopsis - Tian, Huiyu; Wabnik, Krzysztof T; Niu, Tiantian; Li, Hongjiang; Yu, Qianqian; Pollmann, Stephan; Vanneste, Steffen; Govaerts, Willy; Rolčík, Jakub; Geisler, Markus; Friml, Jirí; Ding, Zhaojun (Molecular Plant)
In plants, the patterning of stem cell-enriched meristems requires a graded auxin response maximum that emerges from the concerted action of polar auxin transport, auxin biosynthesis, auxin metabolism, and cellular auxin response machinery. However, mechanisms underlying this auxin response maximum-mediated root stem cell maintenance are not fully understood. Here, we present unexpected evidence that WUSCHEL-RELATED HOMEOBOX 5 (WOX5) transcription factor modulates expression of auxin biosynthetic genes in the quiescent center (QC) of the root and thus provides a robust mechanism for the maintenance of auxin response maximum in the root tip. This WOX5 action is balanced through the activity of indole-3-acetic acid 17 (IAA17) auxin response repressor. Our combined genetic, cell biology, and computational modeling studies revealed a previously uncharacterized feedback loop linking WOX5-mediated auxin production to IAA17-dependent repression of auxin responses. This WOX5-IAA17 feedback circuit further assures the maintenance of auxin response maximum in the root tip and thereby contributes to the maintenance of distal stem cell (DSC) populations. Our experimental studies and in silico computer simulations both demonstrate that the WOX5-IAA17 feedback circuit is essential for the maintenance of auxin gradient in the root tip and the auxin-mediated root DSC differentiation.

Strichartz inequality for orthonormal functions - Frank, Rupert; Lewin, Mathieu; Lieb, Élliott; Seiringer, Robert (Journal of the European Mathematical Society)
We prove a Strichartz inequality for a system of orthonormal functions, with an optimal behavior of the constant in the limit of a large number of functions. The estimate generalizes the usual Strichartz inequality, in the same fashion as the Lieb-Thirring inequality generalizes the Sobolev inequality. As an application, we consider the Schrödinger equation with a time-dependent potential and we show the existence of the wave operator in Schatten spaces.

Lateral junction dynamics lead the way out - Behrndt, Martin; Heisenberg, Carl-Philipp J (Nature Cell Biology)
Epithelial cell layers need to be tightly regulated to maintain their integrity and correct function. Cell integration into epithelial sheets is now shown to depend on the N-WASP-regulated stabilization of cortical F-actin, which generates distinct patterns of apical-lateral contractility at E-cadherin-based cell-cell junctions.

The fitness costs of adaptation via phenotypic plasticity and maternal effects - Ezard, Thomas; Prizak, Roshan; Hoyle, Rebecca (Functional Ecology)
Summary: Phenotypes are often environmentally dependent, which requires organisms to track environmental change. The challenge for organisms is to construct phenotypes using the most accurate environmental cue. Here, we use a quantitative genetic model of adaptation by additive genetic variance, within- and transgenerational plasticity via linear reaction norms and indirect genetic effects respectively. We show how the relative influence on the eventual phenotype of these components depends on the predictability of environmental change (fast or slow, sinusoidal or stochastic) and the developmental lag τ between when the environment is perceived and when selection acts. We then decompose expected mean fitness into three components (variance load, adaptation and fluctuation load) to study the fitness costs of within- and transgenerational plasticity. A strongly negative maternal effect coefficient m minimizes the variance load, but a strongly positive m minimises the fluctuation load. The adaptation term is maximized closer to zero, with positive or negative m preferred under different environmental scenarios. Phenotypic plasticity is higher when τ is shorter and when the environment changes frequently between seasonal extremes. Expected mean population fitness is highest away from highest observed levels of phenotypic plasticity. Within- and transgenerational plasticity act in concert to deliver well-adapted phenotypes, which emphasizes the need to study both simultaneously when investigating phenotypic evolution.

Langerhans cell maturation is accompanied by induction of N-cadherin and the transcriptional regulators of epithelial-mesenchymal transition ZEB1/2 - Konradi, Sabine; Yasmin, Nighat; Haslwanter, Denise; Weber, Michele; Gesslbauer, Bernd; Sixt, Michael K; Strobl, Herbert (European Journal of Immunology)
angerhans cells (LCs) are a unique subset of dendritic cells (DCs) that express epithelial adhesion molecules, allowing them to form contacts with epithelial cells and reside in epidermal/epithelial tissues. The dynamic regulation of epithelial adhesion plays a decisive role in the life cycle of LCs. It controls whether LCs remain immature and sessile within the epidermis or mature and egress to initiate immune responses. So far, the molecular machinery regulating epithelial adhesion molecules during LC maturation remains elusive. Here, we generated pure populations of immature human LCs in vitro to systematically probe for gene-expression changes during LC maturation. LCs down-regulate a set of epithelial genes including E-cadherin, while they upregulate the mesenchymal marker N-cadherin known to facilitate cell migration. In addition, N-cadherin is constitutively expressed by monocyte-derived DCs known to exhibit characteristics of both inflammatory-type and interstitial/dermal DCs. Moreover, the transcription factors ZEB1 and ZEB2 (ZEB is zinc-finger E-box-binding homeobox) are upregulated in migratory LCs. ZEB1 and ZEB2 have been shown to induce epithelial-to-mesenchymal transition (EMT) and invasive behavior in cancer cells undergoing metastasis. Our results provide the first hint that the molecular EMT machinery might facilitate LC mobilization. Moreover, our study suggests that N-cadherin plays a role during DC migration.

Optimality of non-adaptive strategies: The case of parallel games - Demay, Grégory; Gazi, Peter; Maurer, Ueli; Tackmann, Björn (IEEE International Symposium on Information Theory)
Most cryptographic security proofs require showing that two systems are indistinguishable. A central tool in such proofs is that of a game, where winning the game means provoking a certain condition, and it is shown that the two systems considered cannot be distinguished unless this condition is provoked. Upper bounding the probability of winning such a game, i.e., provoking this condition, for an arbitrary strategy is usually hard, except in the special case where the best strategy for winning such a game is known to be non-adaptive. A sufficient criterion for ensuring the optimality of non-adaptive strategies is that of conditional equivalence to a system, a notion introduced in [1]. In this paper, we show that this criterion is not necessary to ensure the optimality of non-adaptive strategies by giving two results of independent interest: 1) the optimality of non-adaptive strategies is not preserved under parallel composition; 2) in contrast, conditional equivalence is preserved under parallel composition.

The rate of adaptation in large sexual populations with linear chromosomes - Weissman, Daniel; Hallatschek, Oskar (Genetics)
In large populations, multiple beneficial mutations may be simultaneously spreading. In asexual populations, these mutations must either arise on the same background or compete against each other. In sexual populations, recombination can bring together beneficial alleles from different backgrounds, but tightly linked alleles may still greatly interfere with each other. We show for well-mixed populations that when this interference is strong, the genome can be seen as consisting of many effectively asexual stretches linked together. The rate at which beneficial alleles fix is thus roughly proportional to the rate of recombination and depends only logarithmically on the mutation supply and the strength of selection. Our scaling arguments also allow us to predict, with reasonable accuracy, the fitness distribution of fixed mutations when the mutational effect sizes are broad. We focus on the regime in which crossovers occur more frequently than beneficial mutations, as is likely to be the case for many natural populations.

Tverberg's Theorem and Graph Coloring - Engström, Alexander; Noren, Patrik (Discrete & Computational Geometry)
The topological Tverberg theorem has been generalized in several directions by setting extra restrictions on the Tverberg partitions. Restricted Tverberg partitions, defined by the idea that certain points cannot be in the same part, are encoded with graphs. When two points are adjacent in the graph, they are not in the same part. If the restrictions are too harsh, then the topological Tverberg theorem fails. The colored Tverberg theorem corresponds to graphs constructed as disjoint unions of small complete graphs. Hell studied the case of paths and cycles. In graph theory these partitions are usually viewed as graph colorings. As explored by Aharoni, Haxell, Meshulam and others there are fundamental connections between several notions of graph colorings and topological combinatorics. For ordinary graph colorings it is enough to require that the number of colors q satisfy q>Δ, where Δ is the maximal degree of the graph. It was proven by the first author using equivariant topology that if q>Δ 2 then the topological Tverberg theorem still works. It is conjectured that q>KΔ is also enough for some constant K, and in this paper we prove a fixed-parameter version of that conjecture. The required topological connectivity results are proven with shellability, which also strengthens some previous partial results where the topological connectivity was proven with the nerve lemma.

Exome sequencing links corticospinal motor neuron disease to common neurodegenerative disorders - Novarino, Gaia; Fenstermaker, Ali; Zaki, Maha; Hofree, Matan; Silhavy, Jennifer; Heiberg, Andrew; Abdellateef, Mostafa; Rosti, Başak; Scott, Eric; Mansour, Lobna; Masri, Amira; Kayserili, Hülya; et al. (Science)
Hereditary spastic paraplegias (HSPs) are neurodegenerative motor neuron diseases characterized by progressive age-dependent loss of corticospinal motor tract function. Although the genetic basis is partly understood, only a fraction of cases can receive a genetic diagnosis, and a global view of HSP is lacking. By using whole-exome sequencing in combination with network analysis, we identified 18 previously unknown putative HSP genes and validated nearly all of these genes functionally or genetically. The pathways highlighted by these mutations link HSP to cellular transport, nucleotide metabolism, and synapse and axon development. Network analysis revealed a host of further candidate genes, of which three were mutated in our cohort. Our analysis links HSP to other neurodegenerative disorders and can facilitate gene discovery and mechanistic understanding of disease.

Cell surface ABP1-TMK auxin sensing complex activates ROP GTPase signaling - Xu, Tongda; Dai, Ning; Chen, Jisheng; Nagawa, Shingo; Cao, Min; Li, Hongjiang; Zhou, Zimin; Chen, Xu; De Rycke, Riet; Rakusová, Hana; Wang, Wen; Jones, Alan; et al. (Science)
Auxin-binding protein 1 (ABP1) was discovered nearly 40 years ago and was shown to be essential for plant development and morphogenesis, but its mode of action remains unclear. Here, we report that the plasma membrane-localized transmembrane kinase (TMK) receptor-like kinases interact with ABP1 and transduce auxin signal to activate plasma membrane-associated ROPs [Rho-like guanosine triphosphatases (GTPase) from plants], leading to changes in the cytoskeleton and the shape of leaf pavement cells in Arabidopsis. The interaction between ABP1 and TMK at the cell surface is induced by auxin and requires ABP1 sensing of auxin. These findings show that TMK proteins and ABP1 form a cell surface auxin perception complex that activates ROP signaling pathways, regulating nontranscriptional cytoplasmic responses and associated fundamental processes.

Distinct cerebellar engrams in short-term and long-term motor learning - Wang, Wen; Nakadate, Kazuhiko; Masugi Tokita, Miwako; Shutoh, Fumihiro; Aziz, Wajeeha; Tarusawa, Etsuko; Lörincz, Andrea; Molnár, Elek; Kesaf, Sebnem; Li, Yunqing; Fukazawa, Yugo; Nagao, Soichi; et al. (PNAS)
Cerebellar motor learning is suggested to be caused by long-term plasticity of excitatory parallel fiber-Purkinje cell (PF-PC) synapses associated with changes in the number of synaptic AMPA-type glutamate receptors (AMPARs). However, whether the AMPARs decrease or increase in individual PF-PC synapses occurs in physiological motor learning and accounts for memory that lasts over days remains elusive. We combined quantitative SDS-digested freeze-fracture replica labeling for AMPAR and physical dissector electron microscopy with a simple model of cerebellar motor learning, adaptation of horizontal optokinetic response (HOKR) in mouse. After 1-h training of HOKR, short-term adaptation (STA) was accompanied with transient decrease in AMPARs by 28% in target PF-PC synapses. STA was well correlated with AMPAR decrease in individual animals and both STA and AMPAR decrease recovered to basal levels within 24 h. Surprisingly, long-termadaptation (LTA) after five consecutive daily trainings of 1-h HOKR did not alter the number of AMPARs in PF-PC synapses but caused gradual and persistent synapse elimination by 45%, with corresponding PC spine loss by the fifth training day. Furthermore, recovery of LTA after 2 wk was well correlated with increase of PF-PC synapses to the control level. Our findings indicate that the AMPARs decrease in PF-PC synapses and the elimination of these synapses are in vivo engrams in short- and long-term motor learning, respectively, showing a unique type of synaptic plasticity that may contribute to memory consolidation.

Rho-GTPase-regulated vesicle trafficking in plant cell polarity - Chen, Xu; Friml, Jirí (Biochemical Society Transactions)
ROPs (Rho of plants) belong to a large family of plant-specific Rho-like small GTPases that function as essential molecular switches to control diverse cellular processes including cytoskeleton organization, cell polarization, cytokinesis, cell differentiation and vesicle trafficking. Although the machineries of vesicle trafficking and cell polarity in plants have been individually well addressed, how ROPs co-ordinate those processes is still largely unclear. Recent progress has been made towards an understanding of the coordination of ROP signalling and trafficking of PIN (PINFORMED) transporters for the plant hormone auxin in both root and leaf pavement cells. PIN transporters constantly shuttle between the endosomal compartments and the polar plasma membrane domains, therefore the modulation of PIN-dependent auxin transport between cells is a main developmental output of ROP-regulated vesicle trafficking. The present review focuses on these cellular mechanisms, especially the integration of ROP-based vesicle trafficking and plant cell polarity.

Distinct kinetics of synaptic structural plasticity, memory formation, and memory decay in massed and spaced learning - Aziz, Wajeeha; Wang, Wen; Kesaf, Sebnem; Mohamed, Alsayed; Fukazawa, Yugo; Shigemoto, Ryuichi (PNAS)
Long-lasting memories are formed when the stimulus is temporally distributed (spacing effect). However, the synaptic mechanisms underlying this robust phenomenon and the precise time course of the synaptic modifications that occur during learning remain unclear. Here we examined the adaptation of horizontal optokinetic response in mice that underwent 1 h of massed and spaced training at varying intervals. Despite similar acquisition by all training protocols, 1 h of spacing produced the highest memory retention at 24 h, which lasted for 1 mo. The distinct kinetics of memory are strongly correlated with the reduction of floccular parallel fiber-Purkinje cell synapses but not with AMPA receptor (AMPAR) number and synapse size. After the spaced training, we observed 25%, 23%, and 12% reduction in AMPAR density, synapse size, and synapse number, respectively. Four hours after the spaced training, half of the synapses and Purkinje cell spines had been eliminated, whereas AMPAR density and synapse size were recovered in remaining synapses. Surprisingly, massed training also produced long-term memory and halving of synapses; however, this occurred slowly over days, and the memory lasted for only 1 wk. This distinct kinetics of structural plasticity may serve as a basis for unique temporal profiles in the formation and decay of memory with or without intervals.

Existence of ground states for negative ions at the binding threshold - Bellazzini, Jacopo; Frank, Rupert; Lieb, Élliott; Seiringer, Robert (Reviews in Mathematical Physics)
As the nuclear charge Z is continuously decreased an N-electron atom undergoes a binding-unbinding transition. We investigate whether the electrons remain bound and whether the radius of the system stays finite as the critical value Zc is approached. Existence of a ground state at Zc is shown under the condition Zc < N-K, where K is the maximal number of electrons that can be removed at Zc without changing the energy.

Plant biology: Gatekeepers of the road to protein perdition - Sauer, Michael; Friml, Jirí (Current Biology)
Targeting membrane proteins for degradation requires the sequential action of ESCRT sub-complexes ESCRT-0 to ESCRT-III. Although this machinery is generally conserved among kingdoms, plants lack the essential ESCRT-0 components. A new report closes this gap by identifying a novel protein family that substitutes for ESCRT-0 function in plants.

A single-molecule approach to explore binding uptake and transport of cancer cell targeting nanotubes - Lamprecht, Constanze; Plochberger, Birgit; Ruprecht, Verena; Wieser, Stefan; Rankl, Christian; Heister, Elena; Unterauer, Barbara; Brameshuber, Mario; Danzberger, Jürgen; Lukanov, Petar; Flahaut, Emmanuel; Schütz, Gerhard; et al. (Nanotechnology)
In the past decade carbon nanotubes (CNTs) have been widely studied as a potential drug-delivery system, especially with functionality for cellular targeting. Yet, little is known about the actual process of docking to cell receptors and transport dynamics after internalization. Here we performed single-particle studies of folic acid (FA) mediated CNT binding to human carcinoma cells and their transport inside the cytosol. In particular, we employed molecular recognition force spectroscopy, an atomic force microscopy based method, to visualize and quantify docking of FA functionalized CNTs to FA binding receptors in terms of binding probability and binding force. We then traced individual fluorescently labeled, FA functionalized CNTs after specific uptake, and created a dynamic 'roadmap' that clearly showed trajectories of directed diffusion and areas of nanotube confinement in the cytosol. Our results demonstrate the potential of a single-molecule approach for investigation of drug-delivery vehicles and their targeting capacity.

Active elastic thin shell theory for cellular deformations - Berthoumieux, Hélène; Maître, Jean-Léon; Heisenberg, Carl-Philipp J; Paluch, Ewa; Julicher, Frank; Salbreux, Guillaume (New Journal of Physics)
We derive the equations for a thin, axisymmetric elastic shell subjected to an internal active stress giving rise to active tension and moments within the shell. We discuss the stability of a cylindrical elastic shell and its response to a localized change in internal active stress. This description is relevant to describe the cellular actomyosin cortex, a thin shell at the cell surface behaving elastically at a short timescale and subjected to active internal forces arising from myosin molecular motor activity. We show that the recent observations of cell deformation following detachment of adherent cells (Maître J-L et al 2012 Science 338 253-6) are well accounted for by this mechanical description. The actin cortex elastic and bending moduli can be obtained from a quantitative analysis of cell shapes observed in these experiments. Our approach thus provides a non-invasive, imaging-based method for the extraction of cellular physical parameters.

Bipolar plasma membrane distribution of phosphoinositides and their requirement for auxin-mediated cell polarity and patterning in Arabidopsis - Tejos, Ricardo; Sauer, Michael; Vanneste, Steffen; Palacios-Gomez, MiriamPalacios; Li, Hongjiang; Heilmann, Mareike; Van Wijk, Ringo; Vermeer, Joop; Heilmann, Ingo; Munnik, Teun; Friml, Jirí (Plant Cell)
Cell polarity manifested by asymmetric distribution of cargoes, such as receptors and transporters, within the plasma membrane (PM) is crucial for essential functions in multicellular organisms. In plants, cell polarity (re)establishment is intimately linked to patterning processes. Despite the importance of cell polarity, its underlying mechanisms are still largely unknown, including the definition and distinctiveness of the polar domains within the PM. Here, we show in Arabidopsis thaliana that the signaling membrane components, the phosphoinositides phosphatidylinositol 4-phosphate (PtdIns4P) and phosphatidylinositol 4, 5-bisphosphate [PtdIns(4, 5)P2] as well as PtdIns4P 5-kinases mediating their interconversion, are specifically enriched at apical and basal polar plasma membrane domains. The PtdIns4P 5-kinases PIP5K1 and PIP5K2 are redundantly required for polar localization of specifically apical and basal cargoes, such as PIN-FORMED transporters for the plant hormone auxin. As a consequence of the polarity defects, instructive auxin gradients as well as embryonic and postembryonic patterning are severely compromised. Furthermore, auxin itself regulates PIP5K transcription and PtdIns4P and PtdIns(4, 5)P2 levels, in particular their association with polar PM domains. Our results provide insight into the polar domain-delineating mechanisms in plant cells that depend on apical and basal distribution of membrane lipids and are essential for embryonic and postembryonic patterning.